Optical laminate, and a polarizing plate, surface plate, and image display device having the same

KR103017063B1Active Publication Date: 2026-09-09DAI NIPPON PRINTING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020227037109
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-30
Publication Date
2026-09-09
Estimated Expiration
2041-03-30

Smart Images

  • Figure 112022112408666-PCT00022_ABST
    Figure 112022112408666-PCT00022_ABST
Patent Text Reader

Abstract

An optical laminate is provided that does not use an adhesive layer of a specific material, has excellent adhesion between a polyester film with a high plane orientation degree ΔP and an adhesive layer, and suppresses local defects. The optical laminate has an adhesive layer, an uneven layer, and an antifouling layer on a polyester film, wherein, when the refractive index in the direction of the ground axis within the plane of the polyester film is defined as nx, the refractive index in the direction orthogonal to the ground axis within the same plane as ny, and the refractive index in the thickness direction of the polyester film as nz, the polyester film satisfies the following Equation 1-2, and when the three-dimensional skewness of the surface of the uneven layer is defined as Ssk and the three-dimensional arithmetic mean roughness of the surface of the uneven layer as Sa, Ssk and Sa satisfy the following Equation 2-1. [In Equation 1-2, “ΔP” represents “((nx+ny) / 2)-nz”.] [In Equation 2-1, "A" represents "log10(Sa[㎛]×100 / Ssk)". However, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present disclosure relates to an optical laminate, and a polarizing plate, a surface plate, and an image display device having the same. Background Technology

[0002] In image display devices such as liquid crystal displays, organic EL displays, micro LED displays, mini LED displays, and quantum dot displays, various optical laminates are arranged for the purpose of improving image visibility and suppressing scratches on the surface of the device. These optical laminates are often configured to have a functional layer, such as an uneven layer, on a plastic film. Furthermore, as the plastic film of the optical laminate, a triacetylcellulose film with low optical anisotropy has been preferably used. In this specification, "triacetylcellulose film" may be referred to as "TAC film."

[0003] However, TAC films have problems with dimensional stability and mechanical strength, and these problems occurred significantly, particularly in large-screen image display devices.

[0004] For this reason, polyester films such as polyethylene terephthalate films have been proposed as alternatives to TAC films. In this specification, "polyethylene terephthalate film" may be referred to as "PET film."

[0005] However, when a PET film is applied to an image display device that outputs polarized light, such as a liquid crystal display and an organic EL display, a rainbow-shaped interference pattern called a rainbow stain occurs due to the in-plane phase difference of the PET film, which reduces visibility.

[0006] As a countermeasure against rainbow stains, a means of making the in-plane phase difference of the PET film very large has been proposed (e.g., Patent Document 1).

[0007] A PET film with a very large in-plane phase difference, such as that described in Patent Document 1, is obtained by uniaxially stretching a PET film. However, uniaxially stretched films have problems such as being prone to tearing in the stretching direction.

[0008] As a countermeasure against rainbow stains, contrary to Patent Document 1, a means of reducing the in-plane phase difference of the PET film is considered. Prior art literature

[0009] Japanese Patent Publication No. 2011-107198 Japanese Patent Publication No. 2012-32819 Japanese Patent Publication No. 2016-6530 The problem to be solved

[0010] PET films with a small in-plane phase difference can be obtained, for example, by lowering the stretching ratio. However, PET films with a low stretching ratio have a problem of lacking practicality because the mechanical strength is reduced due to uneven orientation in the thickness direction.

[0011] In addition, the PET films of Patent Documents 2 and 3 can be cited as having a small in-plane phase difference. The PET films of Patent Documents 2 and 3 have a small in-plane phase difference compared to general-purpose biaxially stretched PET films by reducing the difference in stretching ratio between the flow direction (MD direction) and the width direction (TD direction), etc.

[0012] PET films that have a small in-plane phase difference without a low stretching ratio, as described in Patent Documents 2 and 3, have the characteristic of having a high plane orientation degree ΔP. Since such biaxially stretched PET films with a high plane orientation degree ΔP have poor adhesion of the adhesive layer, there was a problem in that the interface between the PET film and the adhesive layer was prone to delamination when a functional layer was applied on the adhesive layer. The above problem can be solved by applying an adhesive layer made of a material with excellent adhesion. However, the above solution lacks practicality because the range of material choices for the adhesive layer is limited, which creates constraints in product design. Furthermore, when performing the optical design of the entire optical laminate, if an adhesive layer of a specific material exists on the PET film, material constraints on the functional layer formed on the adhesive layer also arise.

[0013] In addition, when a functional layer is formed by interposing an adhesive layer on a biaxially stretched PET film with a high plane orientation ΔP, localized defects may occur in the optical laminate due to differences in local transmittance and reflectance.

[0014] The present disclosure aims to provide, in light of the above problem, an optical laminate that does not use an adhesive layer of a specific material, has excellent adhesion between a polyester film with a high plane orientation degree ΔP and an adhesive layer, and suppresses local defects, and a polarizing plate, a surface plate, and an image display device equipped with the same. means of solving the problem

[0015] To solve the above problem, the present disclosure provides the following [1] to [4].

[0016] [1] On a polyester film, there is an easy-to-adhesion layer, an uneven layer and an anti-fouling layer,

[0017] When the refractive index in the direction of the ground axis within the plane of the polyester film is defined as nx, the refractive index in the direction perpendicular to the ground axis within the same plane as ny, and the refractive index in the thickness direction of the polyester film as nz, the polyester film satisfies the following Equation 1-2, and

[0018] The above-described surface layer is an optical laminate in which, when the three-dimensional skewness of the surface of the surface layer is defined as Ssk and the three-dimensional arithmetic mean roughness of the surface of the surface layer is defined as Sa, Ssk and Sa satisfy the following Equation 2-1.

[0019]

[0020] [In Equation 1-2, “ΔP” represents “((nx+ny) / 2)-nz”.]

[0021] [In Equation 2-1, "A" is "log 10 Represents "(Sa[㎛]×100 / Ssk)". However, 0 <Ssk이다.]

[0022] [2] A polarizing plate having a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is an optical laminate as described in [1], and the optical laminate is disposed such that the side of the antifouling layer faces the opposite side of the polarizer.

[0023] [3] A surface plate for an image display device having an optical laminate bonded to a resin plate or a glass plate, wherein the optical laminate is the optical laminate described in [1] and the optical laminate is positioned such that the side of the antifouling layer faces the opposite side of the resin plate or the glass plate.

[0024] [4] An image display device in which the antifouling layer side of the optical laminate described in [1] is positioned on a display element such that it faces opposite to the display element, and the optical laminate is positioned on the surface. Effects of the invention

[0025] The optical laminate of the present disclosure, and the polarizing plate, surface plate, and image display device equipped with the same, can improve the adhesion between a polyester film with a high plane orientation degree ΔP and an adhesive layer without using an adhesive layer of a specific material, and can also suppress local defects of the optical laminate. Brief explanation of the drawing

[0026] FIG. 1 is a cross-sectional view schematically illustrating one embodiment of an optical laminate of the present disclosure. Specific details for implementing the invention

[0027] Hereinafter, the optical laminate of the present disclosure will be described in detail.

[0028] In addition, the notation of the numerical range “AA to BB” in this specification means “AA or higher and BB or lower.”

[0029] [Optical Laminate]

[0030] The optical laminate of the present disclosure has, on a polyester film, an easy-to-adhesion layer, an uneven surface layer, and an antifouling layer, and

[0031] When the refractive index in the direction of the ground axis within the plane of the polyester film is defined as nx, the refractive index in the direction perpendicular to the ground axis within the same plane as ny, and the refractive index in the thickness direction of the polyester film as nz, the polyester film satisfies the following Equation 1-2, and

[0032] The above-mentioned uneven layer is such that when the three-dimensional skewness of the surface of the uneven layer is defined as Ssk and the three-dimensional arithmetic mean roughness of the surface of the uneven layer is defined as Sa, Ssk and Sa satisfy the following Equation 2-1.

[0033]

[0034] [In Equation 1-2, “ΔP” represents “((nx+ny) / 2)-nz”.]

[0035] [In Equation 2-1, "A" is "log 10 Represents "(Sa[㎛]×100 / Ssk)". However, 0 <Ssk이다.]

[0036] FIG. 1 is a cross-sectional view schematically illustrating one embodiment of an optical laminate of the present disclosure. The optical laminate (100) of FIG. 1 has an easy-to-adhesion layer (20), an uneven layer (30), and an anti-fouling layer (40) in this order on a polyester film (10).

[0037] Polyester film

[0038] A polyester film needs to satisfy the following Equation 1-2, where the refractive index in the direction of the ground axis in the plane is defined as nx, the refractive index in the direction perpendicular to the ground axis in the plane is defined as ny, and the refractive index in the thickness direction of the polyester film is defined as nz.

[0039]

[0040] [In Equation 1-2, “ΔP” represents “((nx+ny) / 2)-nz”.]

[0041] In this specification, refractive indices such as nx, ny, and nz, in-plane phase difference, and thickness direction phase difference are defined as values ​​at a wavelength of 550 nm unless specifically stated otherwise. In this specification, "in-plane phase difference" may be denoted as "Re" and "thickness direction phase difference" as "Rth".

[0042] Equation 1-2

[0043] Equation 1-2 specifies that ΔP, expressed as “((nx+ny) / 2)-nz”, is 0.140 or greater. ΔP is called the plane orientation and is a parameter representing the strength of orientation of the entire plane of the film.

[0044] If ΔP is less than 0.140, the mechanical strength of the polyester film becomes insufficient, and furthermore, physical properties such as pencil hardness of the optical laminate deteriorate.

[0045] It is preferable that ΔP be 0.145 or higher, and more preferable that it be 0.150 or higher. In addition, since recent image display devices have an increasing number of curved designs, when considering pencil hardness and flexibility simultaneously, it is preferable that the lower limit of ΔP be 0.160 or higher, and more preferable that it be 0.176 or higher.

[0046] When ΔP is too large, it may be difficult to make nx-ny 0.0250 or less. For this reason, it is preferable that ΔP be 0.250 or less, more preferable that it be 0.220 or less, and even more preferable that it be 0.200 or less.

[0047] As an embodiment of the range of ΔP, 0.140 or more, 0.140 or more and 0.250 or less, 0.140 or more and 0.220 or less, 0.140 or more and 0.200 or less, 0.145 or more and 0.250 or less, 0.145 or more and 0.220 or less, 0.145 or more and 0.200 or less, 0.150 or more and 0.250 or less, 0.150 or more and 0.220 or less, 0.150 or more and 0.200 or less, 0.160 or more and 0.250 or less, 0.160 or more and 0.220 or less, 0.160 or more and 0.200 or less, 0.176 or more, 0.176 or more and 0.250 or less, 0.176 or more and 0.220 or less, 0.176 or more 0.200 or less can be cited.

[0048] The polyester film of the optical laminate of the present disclosure needs to satisfy Formula 1-2. A polyester film satisfying Formula 1-2 has the physical properties described above, but has poor adhesion. The optical laminate of the present disclosure forms an adhesion-friendly layer and a specific uneven layer in that order on the polyester film satisfying Formula 1-2, and also forms an antifouling layer on the specific uneven layer, thereby improving the adhesion between the polyester film and the adhesion-friendly layer, and further improving the overall adhesion of the optical laminate. The reason why the adhesion of the optical laminate can be improved is described later.

[0049] The nx, ny, and nz of the polyester film, and the in-plane phase difference and thickness direction phase difference described below, can be measured, for example, by the product name “RETS-100” of Otsuka Denshi Co., Ltd.

[0050] In this specification, nx, ny, nz, ΔP, Re, Rth, Sa, Ssk, and A represent the average of 14 measurements, excluding the minimum and maximum values ​​of 16 measurements, unless specifically stated otherwise. Also, “A” is “A” of Equation 2-1.

[0051] In the present specification, the measurement points of 16 are preferably set as the measurement centers by defining a margin of 0.5 cm from the outer edge of the measurement sample and drawing lines that divide the area inside the margin into five equal parts in the vertical and horizontal directions. For example, if the measurement sample is a rectangle, the margin is defined as 0.5 cm from the outer edge of the rectangle, and measurements are performed centering on the 16 intersection points of dotted lines that divide the area inside the margin into five equal parts in the vertical and horizontal directions. Then, the average value of the 14 points excluding the minimum and maximum values ​​is taken as the value of each parameter.

[0052] If the measurement sample has a shape other than a square, such as a circle, ellipse, triangle, or pentagon, it is preferable to draw a square inscribed within the shape and to perform 16 measurements on the square using the above method.

[0053] In this specification, the atmosphere for measuring various parameters shall, unless specifically stated otherwise, have a temperature of 23℃±5℃ and a relative humidity of 40% or more and 65% or less. In addition, unless specifically stated otherwise, a sample shall be exposed to the atmosphere for at least 30 minutes before each measurement.

[0054] 《Essence 1-1》

[0055] It is preferable that the polyester film satisfies Formula 1-1 below.

[0056]

[0057] Equation 1-1 specifies that the difference between the refractive index nx in the direction of the ground axis within the plane of the polyester film and the refractive index ny in the direction of the true axis, which is orthogonal to the ground axis within the same plane, is small.

[0058] If Equation 1-1 is not satisfied and nx-ny exceeds 0.0250, rainbow stains caused by in-plane phase difference cannot be suppressed.

[0059] In this specification, a rainbow stain refers to a rainbow stain as seen with the naked eye, unless otherwise specifically noted.

[0060] In addition, if nx - ny exceeds 0.0250, the difference in the refractive index of the polyester film increases depending on the viewing direction, which increases the degree to which the reflectance of the optical laminate varies along the direction. If the reflectance of the optical laminate varies along the direction, local defects that occur when Equation 2-1 is not satisfied may become easier to detect. By making nx - ny 0.0250 or less, it is easier to suppress the detection of local defects.

[0061] It is more preferable that nx-ny is 0.0240 or less, and even more preferable that it is 0.0230 or less.

[0062] If nx-ny is too small, it is difficult to suppress blackout. For this reason, it is preferable that nx-ny be 0.0050 or higher, more preferable that it be 0.0080 or higher, and even more preferable that it be 0.0100 or higher.

[0063] In this specification, "blackout" refers to a phenomenon in which the entire surface becomes dark when light passing through a polarizer and a polyester film in this order is viewed through polarizing sunglasses.

[0064] In the configuration requirements described in this specification, if multiple options for an upper limit and a lower limit of a numerical value are each provided, one selected from the upper limit options and one selected from the lower limit options can be combined to form an embodiment of the numerical range.

[0065] For example, in the case of nx-ny, embodiments of numerical ranges such as 0.0250 or less, 0.0050 or more and 0.0250 or less, 0.0050 or more and 0.0240 or less, 0.0050 or more and 0.0230 or less, 0.0080 or more and 0.0250 or less, 0.0080 or more and 0.0240 or less, 0.0080 or more and 0.0230 or less, 0.0100 or more and 0.0250 or less, 0.0100 or more and 0.0240 or less, and 0.0100 or more and 0.0230 or less can be cited.

[0066] Other physical properties

[0067] It is preferable that the polyester film has other physical properties, such as in-plane phase difference and thickness direction phase difference, within the following ranges.

[0068] In this specification, the in-plane phase difference and the phase difference in the thickness direction are defined as being calculated by the following formula. In the following formula, "T" represents the thickness of the polyester film.

[0069]

[0070] -In-plane Phase Difference (Re)-

[0071] The polyester film is preferably 1200 nm or less in-plane phase difference, more preferably 1100 nm or less, more preferably 1000 nm or less, and more preferably 950 nm or less.

[0072] By making the in-plane phase difference 1200 nm or less, it is easier to suppress rainbow stains.

[0073] The polyester film is preferably 50 nm or more, more preferably 100 nm or more, more preferably 150 nm or more, more preferably 200 nm or more, more preferably 250 nm or more, more preferably 300 nm or more, and more preferably 400 nm or more.

[0074] By making the in-plane phase difference 50 nm or more, it is easier to suppress blackout. This is because polyester films with an average in-plane phase difference of less than 50 nm transmit linear polarization without scattering it, whereas polyester films with an average in-plane phase difference of 50 nm or more can scatter linear polarization. In addition, to ensure good mechanical strength, such as pencil hardness, of the polyester film, it is preferable that the in-plane phase difference be 520 nm or more, and more preferable that it be 620 nm or more.

[0075] As an embodiment of the range of in-plane phase difference of a polyester film, the range is 50 nm or more and 1200 nm or less, 50 nm or more and 1100 nm or less, 50 nm or more and 1000 nm or less, 50 nm or more and 950 nm or less, 100 nm or more and 1200 nm or less, 100 nm or more and 1100 nm or less, 100 nm or more and 1000 nm or less, 100 nm or more and 950 nm or less, 150 nm or more and 1200 nm or less, 150 nm or more and 1100 nm or less, 150 nm or more and 1000 nm or less, 150 nm or more and 950 nm or less, 200 nm or more and 1200 nm or less, 200 nm or more and 1100 nm or less, 200 nm or more and 1000 nm or less, 200 nm or more and 950 nm or less, 250 nm or more and 1200 nm or less. 250 nm or more and 1100 nm or less, 250 nm or more and 1000 nm or less, 250 nm or more and 950 nm or less, 300 nm or more and 1200 nm or less, 300 nm or more and 1100 nm or less, 300 nm or more and 1000 nm or less, 300 nm or more and 950 nm or less, 400 nm or more and 1200 nm or less, 400 nm or more and 1100 nm or less, 400 nm or more and 1000 nm or less, 400 nm or more and 950 nm or less, 520 nm or more and 1200 nm or less, 520 nm or more and 1100 nm or less, 520 nm or more and 1000 nm or less, 520 nm or more and 950 nm or less, 620 nm or more and 1200 nm or less, 620 nm or more and 1100 nm or less, 620 nm or more and 1000 nm Examples include 620 nm or more and 950 nm or less.

[0076] -Phase difference in thickness direction (Rth)-

[0077] The polyester film preferably has a phase difference in the thickness direction of 2000 nm or more, more preferably 3000 nm or more, even more preferably 4000 nm or more, and even more preferably 5000 nm or more.

[0078] By making the phase difference in the thickness direction of the polyester film 2000 nm or more, it is possible to easily suppress blackout when viewed from an oblique direction as well as from the front direction.

[0079] The phase difference in the thickness direction of the polyester film is preferably 15,000 nm or less, more preferably 12,000 nm or less, and even more preferably 9,000 nm or less, in order to make it easier to make Re / Rth within the range described below.

[0080] Examples of embodiments of the range of phase difference in the thickness direction of the polyester film include 2000 nm or more and 15000 nm or less, 2000 nm or more and 12000 nm or less, 2000 nm or more and 9000 nm or less, 3000 nm or more and 15000 nm or less, 3000 nm or more and 12000 nm or less, 3000 nm or more and 9000 nm or less, 4000 nm or more and 15000 nm or less, 4000 nm or more and 12000 nm or less, 4000 nm or more and 9000 nm or less, 5000 nm or more and 15000 nm or less, 5000 nm or more and 12000 nm or less, and 5000 nm or more and 9000 nm or less.

[0081] -Re / Rth-

[0082] The polyester film preferably has a Re / Rth of 0.20 or less, more preferably 0.17 or less, and even more preferably 0.15 or less.

[0083] A small Re / Rth ratio means that the degree of stretching of the polyester film approaches uniform biaxiality. Therefore, by keeping the above ratio at 0.20 or less, the mechanical strength of the polyester film can be improved, and the adverse effect on visibility caused by wrinkles in the polyester film due to environmental changes can be suppressed. To facilitate the achievement of the aforementioned effects, it is desirable that the in-plane phase difference of the polyester film be within the above range.

[0084] The lower limit of Re / Rth is typically around 0.01.

[0085] Examples of embodiments of the range of Re / Rth include 0.01 or more and 0.20 or less, 0.01 or more and 0.17 or less, and 0.01 or more and 0.15 or less.

[0086] -Haze, Total Light Transmittance-

[0087] The polyester film preferably has a haze of 3.0% or less according to JIS K7136: 2000, more preferably 2.0% or less, and even more preferably 1.0% or less.

[0088] In addition, the polyester film preferably has a total light transmittance of 80% or more according to JIS K7361-1:1997, more preferably 85% or more, and even more preferably 90% or more.

[0089] -UV transmittance-

[0090] The polyester film preferably has a light transmittance of 20% or less at a wavelength of 380 nm, and more preferably 10% or less.

[0091] -thickness-

[0092] In order to ensure good mechanical strength, the thickness of the polyester film is preferably 10 μm or more, more preferably 20 μm or more, even more preferably 25 μm or more, and even more preferably 30 μm or more. In addition, making the thickness of the polyester film 10 μm or more is desirable in that when stress is generated by another member contacting the polyester film side of the optical laminate, it is difficult for said stress to be transmitted to the interface between the polyester film and the adhesive layer.

[0093] In addition, the thickness of the polyester film is preferably 75 μm or less, more preferably 60 μm or less, even more preferably 55 μm or less, and even more preferably 50 μm or less in order to reduce the in-plane phase difference and improve flexibility.

[0094] Examples of embodiments for the thickness range of the plastic film include 10㎛ or more and 75㎛ or less, 10㎛ or more and 60㎛ or less, 10㎛ or more and 55㎛ or less, 10㎛ or more and 50㎛ or less, 20㎛ or more and 75㎛ or less, 20㎛ or more and 60㎛ or less, 20㎛ or more and 55㎛ or less, 20㎛ or more and 50㎛ or less, 25㎛ or more and 75㎛ or less, 25㎛ or more and 60㎛ or less, 25㎛ or more and 55㎛ or less, 25㎛ or more and 50㎛ or less, 30㎛ or more and 75㎛ or less, 30㎛ or more and 60㎛ or less, 30㎛ or more and 55㎛ or less, and 30㎛ or more and 50㎛ or less.

[0095] -Yeonsin-

[0096] In order to make it easier to satisfy Equations 1-1 and 1-2, it is desirable not to lower the elongation ratios in the longitudinal and transverse directions, and to keep the elongation ratios in both directions close.

[0097] For this reason, the polyester film is preferably a stretched film, and more preferably a biaxially stretched film.

[0098] Specific elongation conditions will be described later.

[0099] "raw material"

[0100] Polyesters constituting a polyester film may include a homopolymer obtained from the polycondensation of a dicarboxylic acid and a diol; a copolymer obtained from the polycondensation of one or more dicarboxylic acids and two or more diols; a copolymer obtained from the polycondensation of two or more dicarboxylic acids and one or more diols; and a blend resin obtained by mixing one or more homopolymers and one or more copolymers.

[0101] The polyester film may contain additives such as ultraviolet absorbers, diactive particles such as inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light-resistant agents, flame retardants, heat stabilizers, antioxidants, anti-gelling agents, and surfactants, to the extent that it does not impair the effects of the present disclosure.

[0102] As dicarboxylic acids, for example, terephthalic acid, isophthalic acid, orthophthalic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, diphenylcarboxylic acid, diphenoxyethanedicarboxylic acid, diphenylsulfonecarboxylic acid, anthracenedicarboxylic acid, 1,3-cyclopentanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyladipic acid, Examples include trimethyladipic acid, pimetic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, dodecanedicarboxylic acid, etc.

[0103] Examples of diols include ethylene glycol, propylene glycol, hexamethylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decamethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexadiol, 2,2-bis(4-hydroxyphenyl)propane, bis(4-hydroxyphenyl)sulfone, etc.

[0104] Among polyesters, polyethylene terephthalate is preferred to ensure good mechanical strength. That is, it is preferable for the polyester film to contain polyethylene terephthalate.

[0105] Polymerization methods for polyethylene terephthalate include a direct polymerization method in which terephthalic acid and ethylene glycol are directly reacted with other dicarboxylic acid components and diol components as needed; and an ester exchange method in which a dimethyl ester of terephthalic acid and ethylene glycol are subjected to an ester exchange reaction. In the ester exchange method, the dimethyl ester of terephthalic acid may include a methyl ester of another dicarboxylic acid as needed. In the ester exchange method, the ethylene glycol may include other diol components as needed.

[0106] The intrinsic viscosity of polyethylene terephthalate is preferably 0.45 or higher and 0.70 or lower. If the intrinsic viscosity is lower than 0.45, the effect of improving tear resistance is reduced, and if the intrinsic viscosity is higher than 0.70, high-precision filtration becomes difficult because the increase in filtration pressure increases.

[0107] Layered Composition

[0108] The polyester film may have a single-layer structure or a multi-layer structure.

[0109] A single-layer structure is easy to control elongation. Equations 1-1 and 1-2 are easily satisfied by keeping the elongation ratios in the longitudinal and transverse directions low, and by keeping the elongation ratios in both directions close. For this reason, a single-layer structure that is easy to control elongation is desirable in that it is easy to satisfy Equations 1-1 and 1-2.

[0110] Meanwhile, a multilayer polyester film is desirable in that it can provide effects, for example, by changing the composition of each layer. For example, by making a laminated polyester film consisting of at least three layers by co-extrusion and using a polyester with a low oligomer content in the surface layer, it is easier to suppress the amount of oligomer precipitation on the film surface after heat treatment.

[0111] When using a polyester film with a multilayer structure, the thickness of the surface layer is preferably 3 μm or more, more preferably 5 μm or more, and also 25% or less of the total thickness, more preferably 20% or less, and particularly preferably 10% or less.

[0112] Example of Polyester Film Preparation

[0113] An embodiment of the method for manufacturing a polyester film is described using a PET film as an example.

[0114] First, the PET pellets are thoroughly vacuum dried. The vacuum-dried PET pellets are fed into an extruder, melt-extruded into a sheet shape at a temperature between 260°C and 290°C, and then cooled and solidified to form an unoriented PET sheet. At this time, high-precision filtration is performed to remove foreign substances contained in the resin at any location where the molten resin is maintained at a temperature between 260°C and 290°C. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a sintered stainless steel filter material is preferred. A sintered stainless steel filter material has excellent removal performance for aggregates and high-melting point organic matter composed mainly of Si, Ti, Sb, Ge, and Cu. In addition, the filter particle size of the filter material is preferably 15㎛ or less. The above filter particle size is the value at an initial filtration efficiency of 95%.

[0115] In the extrusion method, an unoriented sheet is obtained by melting PET from an extrusion die, extruding it, and then cooling and solidifying it with a cooling roll. If necessary, polyester resin layers may be laminated using two or three extruders, a two- or three-layer multi-manifold, or a feed block. To improve the flatness of the sheet, it is preferable to use an electrostatic application adhesion method or a liquid coating adhesion method to increase the adhesion between the sheet and the rotary cooling drum.

[0116] A uniaxially oriented PET film is obtained by stretching the unoriented film obtained by the above in the longitudinal direction with a roll heated to 70°C or higher and 120°C or lower. If you want to reduce the deformation of the orientation main axis due to the so-called bowing phenomenon, you may adopt a method of lowering the longitudinal stretching ratio or setting the stretching temperature high within a range where there is no problem with thickness non-uniformity.

[0117] In addition, the surface temperature at the start of stretching is preferably 80°C or higher and 93°C or lower. Since orientation and crystallization do not proceed too much in this temperature range during the initial stage of stretching, it can be said to be a desirable ΔP.

[0118] Next, the ends of the film are clipped and guided into a hot air zone heated to a temperature of 70°C or higher and 200°C or lower, and after drying, the film is stretched in the width direction. Subsequently, the film is guided into a heat treatment zone within the range of heat fixation temperatures described later, and heat treatment is performed to complete the crystal orientation. During this heat treatment process, if necessary, a relaxation treatment of 2% or more and 10% or less in the width direction or the length direction may be performed.

[0119] In addition, PET film may be manufactured by simultaneous biaxial stretching instead of sequential biaxial stretching as described above.

[0120] When stretching the film, the stretching ratio is preferably 2 times or more and 6.5 times or less in both the length direction and the width direction, more preferably 2.5 times or more and 5.5 times or less, and more preferably 3 times or more and 4.8 times or less.

[0121] By making the film stretching ratio 2 times or more, it is easier to satisfy Equation 1-2. In addition, by making the film stretching ratio 6.5 times or less, it is easier to suppress ΔP from becoming too large, and furthermore, it is easier to suppress wrinkles and cracks during film formation.

[0122] The ratio of the lengthwise elongation ratio to the widthwise elongation ratio, "lengthwise elongation ratio / widthwise elongation ratio," is preferably 1.7 or less, and more preferably 1.4 or less. Additionally, the ratio is preferably 0.5 or more, more preferably 0.7 or more, and even more preferably 1.0 or more.

[0123] By setting the lengthwise elongation ratio / widthwise elongation ratio to the above range, it is easier to satisfy Equation 1-1.

[0124] In addition, when sequential stretching is employed, the orientation of the film tends to be strongly influenced by the stretching direction of the last stage. For this reason, in sequential stretching, it is desirable to make the stretching ratio in the length direction higher than the stretching ratio in the width direction.

[0125] In addition, when employing sequential stretching, it is desirable to perform stretching in the width direction in at least two stages. In particular, it is desirable to perform stretching in the width direction in two or more stages with different stretching temperatures. In this case, it is desirable to perform the stretching in the later stage at a higher temperature, preferably 5°C or higher, and more preferably 10°C or higher, than the stretching temperature of the earlier stage. Since the deformation of optical properties caused by bowing in the width direction occurring in the earlier stage can be mitigated by the high-temperature stretching process in the later stage, fluctuations in the in-plane phase difference in the width direction can be suppressed. Furthermore, when stretching in width in two stages, it is desirable to make the stretching ratio in the later stage lower than the stretching ratio in the earlier stage. By lowering the stretching ratio in the later stage, the deterioration of thickness non-uniformity of the film can be suppressed. Specifically, when performing width stretching in two stages, it is preferable to perform the first stage stretching at a range of 1.5 to 4.5 times in the range of 120°C to 200°C, and then re-stretch at a ratio of 1.01 to 2.0 times in the range of 150°C to 230°C. Below, the first stage stretching is performed in the range of 120°C to 200°C, and the second stage stretching is performed in the range of 150°C to 230°C. The first stage stretching may be referred to as TD1, and the second stage stretching as TD2.

[0126] When performing two-stage stretching within the above range, the stretching temperature of TD1 is preferably 120°C or higher and 200°C or lower, and more preferably 130°C or higher and 150°C or lower. If the temperature is 120°C or lower, the film breaks, and if it is 200°C or higher, the deformation of the film's physical properties in the width direction increases. The stretching ratio is preferably 1.5 times or higher and 4.5 times or lower. In addition, the stretching temperature of TD2 is preferably 150°C or higher and 230°C or lower, and more preferably 180°C or higher and 220°C or lower. The stretching ratio is preferably 1.01 times or higher and 2.0 times or lower.

[0127] In this way, by performing both stages of stretching in a temperature range of 120°C or higher and 230°C or lower, and by setting the sum of the two stages of stretching ratio to 3.0 times or higher and 4.8 times or lower, it is possible to reduce fluctuations in the in-plane phase difference in the width direction while maintaining plane orientation capable of maintaining mechanical strength.

[0128] In order to improve the thermal dimensional stability of the film, it is desirable to perform heat setting at a high temperature. Specifically, it is desirable for the upper limit of the heat setting temperature to exceed 130°C, and more desirable for it to be 160°C or higher. However, if the heat setting temperature is performed at a high temperature, the influence of optical distortion caused by bowing is likely to occur, and fluctuations in the in-plane phase difference may increase. Therefore, it is desirable for the upper limit of the heat setting temperature to be 220°C or lower.

[0129] Easy-to-adhesion layer

[0130] The optical laminate of the present disclosure requires having an easy-to-adhere layer between a polyester film and an uneven layer.

[0131] If an easy-to-adhesion layer is not provided, the overall adhesion of the optical laminate cannot be improved even if the uneven surface layer and antifouling layer described later are provided.

[0132] The resin constituting the easy-adhesion layer is not particularly limited and may include, for example, thermoplastic resins such as polyester resin, polyurethane resin, and acrylic resin, as well as thermosetting resin, and thermoplastic resin is preferred. Furthermore, among thermoplastic resins, polyester resin and polyurethane resin are preferred as they facilitate reducing the difference in refractive index between the polyester film and the easy-adhesion layer and the difference in refractive index between the easy-adhesion layer and the uneven layer, and polyester-urethane resin is more preferred.

[0133] The resin constituting the adhesive layer preferably has a number average molecular weight of 10,000 or more, and more preferably 20,000 or more. The resin preferably has a number average molecular weight of 100,000 or less, and more preferably 60,000 or less. By setting the number average molecular weight of the resin constituting the adhesive layer to the above range, it is easier to suppress the cohesive breakdown of the adhesive layer.

[0134] Preferred ranges for the number average molecular weight of the resin constituting the adhesive layer include 10,000 or more and 100,000 or less, 10,000 or more and 60,000 or less, 20,000 or more and 100,000 or less, and 20,000 or more and 60,000 or less.

[0135] The resin constituting the adhesive layer preferably has a glass transition temperature of 30°C or higher, more preferably 50°C or higher, and even more preferably 70°C or higher. The resin preferably has a glass transition temperature of 120°C or lower, more preferably 110°C or lower, and even more preferably 90°C or lower. By setting the glass transition temperature of the resin constituting the adhesive layer to the above range, it is easier to suppress the embrittlement of the adhesive layer caused by heat during the process. Examples of heat during the process include heat during the drying process of the surface texture coating solution and the antifouling coating solution, and heat caused by heating when bonding the optical laminate to the polarizer.

[0136] Preferred ranges for the glass transition temperature of the resin constituting the adhesive layer include 30°C or higher and 120°C or lower, 30°C or higher and 110°C or lower, 30°C or higher and 90°C or lower, 50°C or higher and 120°C or lower, 50°C or higher and 110°C or lower, 50°C or higher and 90°C or lower, 70°C or higher and 120°C or lower, 70°C or higher and 110°C or lower, and 70°C or higher and 90°C or lower.

[0137] The adhesive layer may contain additives such as refractive index modifiers, dyes, pigments, leveling agents, ultraviolet absorbers, antioxidants, and light stabilizers, to the extent that it does not impair the effects of the present disclosure; and various crosslinking agents for adjusting hardness or viscosity. Examples of the crosslinking agents include non-yellowing type XDI-based, IPDI-based, and HDI-based isocyanates, and ionizing radiation-curable polyfunctional monomers.

[0138] The easy-to-adhesion layer may be formed by an inline coating method applied during the formation of the polyester film, or by an offline coating method applied after the formation of the polyester film.

[0139] The dry coating amount of the easy-adhesion layer is preferably 0.05 g / m² or more and 0.75 g / m² or less. The thickness of the easy-adhesion layer is not particularly limited, but it is preferably 10 nm or more and 600 nm or less. In order to prevent poor visibility caused by a difference in refractive index at each interface when a polyester film, an easy-adhesion layer, an uneven surface layer, and an anti-fouling layer are laminated, the thickness of the easy-adhesion layer is preferably 10 nm or more and 40 nm or less, or 70 nm or more and 270 nm or less.

[0140] Uneven surface

[0141] The optical laminate of the present disclosure has an uneven layer on an easy-to-adhesion layer.

[0142] Equation 2-1

[0143] When the three-dimensional skewness of the surface of the uneven layer is defined as Ssk and the three-dimensional arithmetic mean roughness of the surface of the uneven layer is defined as Sa, it is required that Ssk and Sa satisfy Equation 2-1 below.

[0144]

[0145] [In Equation 2-1, "A" is "log 10 Represents "(Sa[㎛]×100 / Ssk)". However, 0 <Ssk이다.]

[0146] In this specification, Ssk is a three-dimensional extension of the skewness Rsk of the roughness curve of the two-dimensional roughness parameter described in JIS B0601:1994, and is calculated by the following formula a, where the orthogonal coordinate axes X and Y are placed on a reference plane, the measured surface shape curve is z = f(x, y), and the dimensions of the reference plane are Lx and Ly. Ssk is defined in ISO 25178:2012.

[0147] Ssk is an indicator representing the degree of skewness in the positive and negative directions of the elevation distribution, based on the average value of the elevation of the entire measurement area. When the elevation distribution follows a normal distribution, Ssk represents 0. If the elevation distribution is skewed in the negative direction, Ssk represents a positive value, and as the degree of skewness in the negative direction of the elevation distribution increases, the value of Ssk increases in the positive direction. On the other hand, if the elevation distribution is skewed in the positive direction, Ssk represents a negative value, and as the degree of skewness in the positive direction of the elevation distribution increases, the value of Ssk increases in the negative direction.

[0148]

[0149] In Equation a, “Sq” is the root mean square deviation of the surface height distribution defined by Equation b below.

[0150]

[0151] In this specification, Sa is a three-dimensional extension of the arithmetic mean roughness Ra of the two-dimensional roughness parameters described in JIS B0601:1994, and is calculated by the following formula c when the orthogonal coordinate axes X and Y are placed on a reference plane and the roughness surface is denoted as Z(x, y). Sa is defined in ISO 25178:2012.

[0152]

[0153] In equation c, Ar = Lx × Ly.

[0154] "A" in Equation 2-1 is, "log 10 It appears as (Sa[㎛]×100 / Ssk)」

[0155] Therefore, it can be said that “A” in Equation 2-1 represents a very small value in any of the following cases from x-1 to x3.

[0156] x-1: Case where Sa is too small.

[0157] x-2: When Ssk is too large.

[0158] x-3: When Sa is appropriately small and Ssk is also appropriately large.

[0159] When Sa of the uneven layer is too small, as in x-1, the unevenness of the uneven layer is hardly reflected on the surface of the antifouling layer, and the surface of the optical laminate, which is the surface of the antifouling layer, becomes approximately smooth. When another member comes into contact with the optical laminate having an approximately smooth surface shape, stress is applied in a state where the other member is attached to the surface of the optical laminate, and thus the stress is transmitted to the interface between the polyester film and the adhesive layer without being significantly relieved. For this reason, when Sa of the uneven layer is too small, as in x-1, there are cases where the adhesion of the interface between the polyester film and the adhesive layer cannot be made good.

[0160] Furthermore, when the Ssk of the uneven layer is too large, as in x-2, the uneven layer has a very high proportion of seabed areas with elevations lower than the average. As a result, the surface of the optical laminate, which is the surface of the antifouling layer, takes on a shape with a very high proportion of seabed areas. When another component comes into contact with an optical laminate having a surface shape with an extremely high proportion of seabed areas, stress is applied in a state where the other component adheres to the seabed areas of the optical laminate; consequently, this stress is transmitted to the interface between the polyester film and the adhesive layer without being significantly relieved. For this reason, if the Ssk of the uneven layer is too large, as in x-2, it may not be possible to ensure good adhesion at the interface between the polyester film and the adhesive layer. Additionally, when an antifouling layer is formed on an uneven layer with an excessively large Ssk, while the antifouling layer is sufficiently formed at locations corresponding to the seabed areas of the uneven layer, it is difficult to form the antifouling layer at locations corresponding to the island areas of the uneven layer, resulting in thickness non-uniformity in the antifouling layer. For this reason, localized defects may occur in the optical laminate due to the occurrence of bright spots caused by differences in transmittance or reflectance between locations corresponding to the sea area and locations corresponding to the island area.

[0161] In addition, as in x-3, when Sa is appropriately small and Ssk is appropriately large, the surface shape indicates that the degree of unevenness is small and the ratio of sea area to island area is appropriately high. When another member comes into contact with an optical laminate with such a surface shape, stress is applied in a state where the other member adheres to the sea area of ​​the optical laminate, so the stress is transmitted to the interface between the polyester film and the adhesive layer with almost no reduction. For this reason, as in x-3, when Sa is appropriately small and Ssk is appropriately large, there are cases where the adhesion of the interface between the polyester film and the adhesive layer cannot be made good.

[0162] In addition, "A" in Equation 2-1 can be said to represent a very large value in any of the following cases y-1 to y3.

[0163] y-1: Case where Sa is too large.

[0164] y-2: When Ssk is too small.

[0165] y-3: When Sa is appropriately large and Ssk is also appropriately small.

[0166] When Sa of the uneven layer is too large, as in y-1, the antifouling layer is sufficiently formed at locations corresponding to the sea portion of the uneven layer, whereas it is difficult to form the antifouling layer at locations corresponding to the island portion of the uneven layer, so thickness non-uniformity occurs in the antifouling layer. Because of this, local defects may occur in the optical laminate, such as bright spots caused by differences in transmittance or reflectance between locations corresponding to the sea portion and locations corresponding to the island portion.

[0167] In addition, when the Ssk of the uneven layer is too small, as in y-2, the ratio of the islands to the seas of the uneven layer approaches 1:1, and furthermore, the ratio of the islands to the seas of the surface of the optical laminate approaches 1:1. Since the islands are easier for other members to contact than the seas, they are more likely to adhere. For this reason, when another member comes into contact with an optical laminate with a surface shape in which the Ssk of the uneven layer is too small, as in y-2, stress is applied in a state where the other member adheres to the islands of the optical laminate, and thus the stress is transmitted to the interface between the polyester film and the adhesive layer without being significantly reduced. Therefore, when the Ssk of the uneven layer is too small, as in y-2, there are cases where the adhesion of the interface between the polyester film and the adhesive layer cannot be improved.

[0168] In addition, as in y-3, when Sa is appropriately large and Ssk is appropriately small, the surface shape indicates that the unevenness is appropriately large and the ratio of the sea area to the island area is not too high. Although the problem of unevenness is unlikely to occur in an optical laminate with such a surface shape, the antifouling layer is sufficiently formed at locations corresponding to the sea area of ​​the unevenness layer, whereas it is difficult to form an antifouling layer at locations corresponding to the island area of ​​the unevenness layer, so thickness non-uniformity occurs in the antifouling layer. Because of this, local defects may occur in the optical laminate, such as bright spots caused by differences in transmittance or reflectance between locations corresponding to the sea area and locations corresponding to the island area.

[0169] From the above, if Equation 2-1 is not satisfied, the adhesion at the interface between the polyester film and the easy-to-adhesion layer cannot be improved. Furthermore, if Equation 2-1 is not satisfied, thickness non-uniformity occurs in the antifouling layer, and localized problems such as bright spots occur due to differences in transmittance or reflectance. In other words, if Equation 2-1 is not satisfied, the problem of localized defects in the optical laminate cannot be suppressed.

[0170] In Formula 2-1, A is preferably 0.90 or higher, more preferably 0.95 or higher, and even more preferably 1.00 or higher. Additionally, in Formula 2-1, A is preferably 1.75 or lower, more preferably 1.65 or lower, and even more preferably 1.60 or lower.

[0171] Examples of embodiments of the range of A in Formula 2-1 include 0.80 or more and 1.90 or less, 0.80 or more and 1.75 or less, 0.80 or more and 1.65 or less, 0.80 or more and 1.60 or less, 0.90 or more and 1.90 or less, 0.90 or more and 1.75 or less, 0.90 or more and 1.65 or less, 0.90 or more and 1.60 or less, 0.95 or more and 1.90 or less, 0.95 or more and 1.75 or less, 0.95 or more and 1.65 or less, 0.95 or more and 1.60 or less, 1.00 or more and 1.90 or less, 1.00 or more and 1.75 or less, 1.00 or more and 1.65 or less, and 1.00 or more and 1.60 or less.

[0172] In this specification, the measurement of Ssk and Sa is performed in an area of ​​0.26 mm on each side (where Lx and Ly in formulas a to c are 0.26 mm). The vertical and horizontal lengths of the area for measuring Ssk and Sa do not need to match perfectly and may differ slightly. The measurement area of ​​the example is 258 µm × 259 µm. Furthermore, in this specification, Ssk and Sa refer to values ​​measured without setting a cutoff value.

[0173] Ssk and Sa can be measured, for example, by a laser microscope-type surface shape measuring instrument. An example of a laser microscope-type surface shape measuring instrument is the Olympus product name "LEXT OLS4000".

[0174] Equation 2-2

[0175] It is desirable that the uneven surface layer satisfies the following formula 2-2.

[0176]

[0177] By making Ssk between 0.10 and 1.50, it is easier to satisfy Equation 2-1.

[0178] It is more preferable that Ssk be 0.12 or higher, and even more preferable that Ssk be 0.15 or higher. Additionally, it is more preferable that Ssk be 1.00 or lower, 0.90 or lower, 0.70 or lower, and 0.55 or lower.

[0179] Examples of embodiments of the range of Ssk include 0.10 or more and 1.50 or less, 0.10 or more and 1.00 or less, 0.10 or more and 0.90 or less, 0.10 or more and 0.70 or less, 0.10 or more and 0.55 or less, 0.12 or more and 1.50 or less, 0.12 or more and 1.00 or less, 0.12 or more and 0.90 or less, 0.12 or more and 0.70 or less, 0.12 or more and 0.55 or less, 0.15 or more and 1.50 or less, 0.15 or more and 1.00 or less, 0.15 or more and 0.90 or less, 0.15 or more and 0.70 or less, and 0.15 or more and 0.55 or less.

[0180] 《Essence 2-3》

[0181] It is desirable that the uneven surface layer satisfies the following formula 2-3.

[0182]

[0183] By making Sa 0.020㎛ or more and 0.200㎛ or less, it is easier to satisfy Equation 2-1.

[0184] It is more preferable that Sa be 0.030㎛ or larger, and even more preferable that Sa be 0.040㎛ or larger. In addition, it is more preferable that Sa be 0.150㎛ or smaller, even more preferable that Sa be 0.100㎛ or smaller, and even more preferable that Sa be 0.085㎛ or smaller.

[0185] Examples of embodiments of the range of Sa include 0.020㎛ or more and 0.200㎛ or less, 0.020㎛ or more and 0.150㎛ or less, 0.020㎛ or more and 0.100㎛ or less, 0.020㎛ or more and 0.085㎛ or less, 0.030㎛ or more and 0.200㎛ or less, 0.030㎛ or more and 0.150㎛ or less, 0.030㎛ or more and 0.100㎛ or less, 0.030㎛ or more and 0.085㎛ or less, 0.040㎛ or more and 0.200㎛ or less, 0.040㎛ or more and 0.150㎛ or less, 0.040㎛ or more and 0.100㎛ or less, and 0.040㎛ or more and 0.085㎛ or less.

[0186] It is preferable that the uneven surface layer includes a binder resin and particles.

[0187] Binder Susie

[0188] It is preferable that the binder resin includes a cured product of a curable resin composition. Examples of the cured product of the curable resin composition include a cured product of a thermosetting resin composition and a cured product of an ionizing radiation-curable resin composition, and a cured product of an ionizing radiation-curable resin composition is preferred to improve mechanical strength.

[0189] The ratio of the cured product of the curable resin composition to the total binder resin of the uneven layer is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, and even more preferably 100 mass%.

[0190] The thermosetting resin composition is a composition comprising at least a thermosetting resin, and is a resin composition that hardens upon heating.

[0191] Examples of thermosetting resins include acrylic resin, urethane resin, phenolic resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to these curable resins as needed.

[0192] An ionizing radiation curable resin composition is a composition comprising a compound having an ionizing radiation curable functional group. In this specification, "a compound having an ionizing radiation curable functional group" may be referred to as "an ionizing radiation curable compound."

[0193] Ionizing radiation refers to electromagnetic waves or charged particle rays that have energy quanta capable of polymerizing or crosslinking molecules. Typically, ultraviolet rays or electron rays are used, but other electromagnetic waves such as X-rays and γ-rays, and charged particle rays such as α-rays and ion rays can also be used.

[0194] Examples of ionizing radiation-curable functional groups include ethylenically unsaturated bonding groups such as (meth)acryloyl groups, vinyl groups, and allyl groups, as well as epoxy groups and oxetanyl groups. As for the ionizing radiation-curable compound, a compound having ethylenically unsaturated bonding groups is preferred, a compound having two or more ethylenically unsaturated bonding groups is more preferred, and among these, a polyfunctional (meth)acrylate-based compound having two or more ethylenically unsaturated bonding groups is even more preferred.

[0195] As for the polyfunctional (meth)acrylate-based compound, both monomers and oligomers may be used, but it is preferable to include an oligomer. That is, it is preferable for the surface layer to include a cured product of a polyfunctional (meth)acrylate oligomer as a binder resin. Since the cured product of the polyfunctional (meth)acrylate oligomer can suppress excessive curing shrinkage of the surface layer while maintaining good surface hardness of the optical laminate, it is possible to prevent the elevation difference of the surface layer containing particles from becoming excessive. For this reason, by including the cured product of the polyfunctional (meth)acrylate oligomer in the surface layer, it is easier to suppress the excessive increase of Ssk and Sa.

[0196] On the other hand, since oligomers have a higher viscosity than monomers, the leveling properties of the coating solution for the uneven layer may be reduced, and the Ssk may increase. For this reason, it is more preferable to include both an oligomer and a monomer as the polyfunctional (meth)acrylate-based compound. That is, it is preferable for the uneven layer to include a cured product of a polyfunctional (meth)acrylate oligomer and a cured product of a polyfunctional (meth)acrylate monomer as the binder resin.

[0197] When using an oligomer and a monomer as a polyfunctional (meth)acrylate-based compound, the mass ratio of the oligomer to the monomer is preferably 20:80 to 80:20, more preferably 20:80 to 60:40 or 40:60 to 80:20, and even more preferably 40:60 to 60:40.

[0198] Examples of multifunctional (meth)acrylate oligomers include (meth)acrylate-based polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate.

[0199] Urethane (meth)acrylate is obtained, for example, by the reaction of polyhydric alcohols and organic diisocyanates with hydroxy (meth)acrylates.

[0200] The weight average molecular weight of the polyfunctional (meth)acrylate oligomer is preferably 500 or higher, more preferably 1000 or higher, preferably 5000 or lower, and more preferably 3000 or lower.

[0201] By making the weight average molecular weight of the oligomer 500 or more, it is easier to suppress excessive curing shrinkage of the uneven layer. In addition, by making the weight average molecular weight of the oligomer 5000 or less, it is easier to suppress the reduction in the leveling properties of the coating solution for the uneven layer and the excessive increase in Ssk.

[0202] Examples of the range of weight average molecular weight of the functional (meth)acrylate oligomer include 500 or more and 5000 or less, 500 or more and 3000 or less, 1000 or more and 5000 or less, and 1000 or more and 3000 or less.

[0203] In this specification, weight average molecular weight and number average molecular weight refer to polystyrene equivalent values ​​measured by gel permeation chromatography.

[0204] Among polyfunctional (meth)acrylate compounds, examples of difunctional (meth)acrylate monomers include ethylene glycol di(meth)acrylate, bisphenol A tetraethoxydiaacrylate, bisphenol A tetrapropoxydiaacrylate, 1,6-hexanediol diacrylate, etc.

[0205] Examples of (meth)acrylate monomers with three or more functional groups include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol tetra(meth)acrylate, isocyanuric acid modified tri(meth)acrylate, etc.

[0206] The above (meth)acrylate monomer may have a part of its molecular backbone modified. For example, (meth)acrylate monomers modified by ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, etc. may also be used.

[0207] In addition, monofunctional (meth)acrylates may be added as ionizing radiation-curable compounds for purposes such as adjusting the viscosity of the coating solution for the uneven surface layer.

[0208] Examples of monofunctional (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, and isobornyl (meth)acrylate.

[0209] The above-mentioned ionizing radiation-curable compound can be used as a single type or in combination of two or more types.

[0210] In addition, the coating solution for the uneven layer may have a polymer added to adjust the viscosity in addition to the ionizing radiation-curable compound. Examples of polymers include those with a weight average molecular weight of more than 5,000 and less than or equal to 200,000.

[0211] When the ionizing radiation-curable compound is a UV-curable compound, it is preferable that the ionizing radiation-curable composition include additives such as a photopolymerization initiator or a photopolymerization promoter.

[0212] As photopolymerization initiators, one or more selected from acetophenone, benzophenone, α-hydroxyalkylphenone, methyl ketone, benzoin, benzyldimethyl ketal, benzoyl benzoate, α-acyloxime ester, anthraquinone, halogenoketone, thioxantones, etc. Among these, α-hydroxyalkylphenone, which is resistant to yellowing, is preferred.

[0213] The photopolymerization accelerator is capable of reducing polymerization inhibition by air during curing and increasing the curing speed, and one or more selected from, for example, p-dimethylaminobenzoate isoamyl ester, p-dimethylaminobenzoate ethyl ester, etc.

[0214] "particle"

[0215] Examples of particles include organic particles, inorganic particles, and metallic particles. Among these, organic and inorganic particles are preferred.

[0216] Examples of organic particles include particles composed of polymethyl methacrylate, polyacryl-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorinated resin, and polyester resin. Organic particles are preferred because they have good dispersibility, making it easy to control Sa and Ssk.

[0217] The average particle size of the organic particles is preferably 0.5㎛ or more at the lower limit, more preferably 1.0㎛ or more, and even more preferably 2.0㎛ or more at the upper limit, preferably 5.0㎛ or less, more preferably 4.0㎛ or less, and even more preferably 3.0㎛ or less.

[0218] By making the average particle size of the organic particles 0.5 μm or larger, it is easier to suppress the excessive decrease in Sa. In addition, when the mass-based content of organic particles is the same, the number of organic particles decreases as the average particle size increases. For this reason, if the average particle size of the organic particles is too large, Ssk tends to increase as independent, steeply convex parts are more likely to form. Therefore, by making the average particle size of the organic particles 5.0 μm or smaller, it is easier to suppress the excessive increase in Ssk.

[0219] Examples of embodiments of the range of average particle size of organic particles include 0.5㎛ or more and 5.0㎛ or less, 0.5㎛ or more and 4.0㎛ or less, 0.5㎛ or more and 3.0㎛ or less, 1.0㎛ or more and 5.0㎛ or less, 1.0㎛ or more and 4.0㎛ or less, 1.0㎛ or more and 3.0㎛ or less, 2.0㎛ or more and 5.0㎛ or less, 2.0㎛ or more and 4.0㎛ or less, and 2.0㎛ or more and 3.0㎛ or less.

[0220] The average particle size of the organic particles can be calculated, for example, by the following operations (A1) to (A3).

[0221] (A1) A transmission observation image of the optical laminate is captured using an optical microscope. The magnification is preferably 500x or more and 2000x or less.

[0222] (A2) After extracting 10 random organic particles from the observed image, the particle diameter of each organic particle is calculated. The particle diameter is measured as the distance between two lines in a combination of two lines where the distance between the two lines is maximized when the cross-section of the particle is fitted between two randomly parallel lines.

[0223] (A3) After performing the same operation 5 times on separate screen observation images of the same sample, the value obtained from the number average of 50 particle sizes is taken as the average particle size of the organic particles.

[0224] It is preferable that the organic particles have a coefficient of variation of particle size of 13% or less, more preferable that it is 12% or less, and even more preferable that it is 11% or less.

[0225] By keeping the coefficient of variation of the particle size of organic particles at 13% or less, Sa and Ssk can be easily controlled.

[0226] The coefficient of variation of the particle size of the organic particle can be obtained from the standard deviation calculated from the 50 particles used to calculate the average particle size of (A1) to (A3) above, and the average particle size, by the following formula.

[0227] Coefficient of variation (%) = (Standard deviation / Average particle size) × 100

[0228] Examples of inorganic particles include particles composed of silica, alumina, zirconia, and titania. Among these, silica is preferred to ensure good transparency. Furthermore, among silicas, fumed silica is preferred.

[0229] Fumed silica is amorphous silica with a particle size of 200 nm or less produced by a dry method, and can be obtained by reacting a silicon-containing volatile compound in the gas phase. Specifically, examples include those produced by hydrolyzing silicon compounds, such as silicon tetrachloride, in a flame of oxygen and hydrogen. Fumed silica is suitable in that its surface can be easily hydrophobized.

[0230] When inorganic particles are used alone, it is desirable for multiple inorganic particles to form aggregates, and for said aggregates to impart irregularities to the uneven surface layer.

[0231] In addition, by performing a hydrophobization treatment on the inorganic particles, aggregates can be formed so that the inorganic particles adhere to the organic particles. For this reason, when comparing a system with only organic particles and a system with both organic and inorganic particles, the system with both organic and inorganic particles tends to have a larger Sa. On the other hand, since inorganic particles form smooth irregularities, when comparing a system with only organic particles and a system with both organic and inorganic particles, the system with both organic and inorganic particles tends to have a smaller Ssk.

[0232] In addition, when inorganic particles are used alone, compared to when organic particles are used alone, the height of the convex portion is lower, and the overall uneven shape tends to be gentle.

[0233] It is preferable that the surface of the inorganic particles be hydrophobized. By hydrophobizing the surface of the inorganic particles, excessive aggregation of the inorganic particles can be suppressed. In addition, by using inorganic particles with hydrophobized surfaces in combination with organic particles, it is possible to make it easier to increase Sa and Ssk as described above.

[0234] Inorganic particles with a hydrophobically treated surface can be defined as having a surface functional group of the inorganic particle and a reaction product of a surface treatment agent on the surface of the inorganic particle. Examples of functional groups on the surface of the inorganic particle include the silanol groups of silica particles.

[0235] As surface treatment agents, one or more selected from trimethylsilyl chloride, dimethyl dichlorosilane, trimethylsilyl trifluoromethanesulfonate, chloromethyltrimethylsilane, hexamethyldisilazane, triethylsilane, triethylsilyl chloride, triisopropylsilyl chloride, t-butyldimethylsilane, t-butyldimethylsilyl chloride, octylsilane, hexadecylsilane, allyltrimethylsilane, trimethylvinylsilane, aminosilane, methacrylsilane, and polydimethylsiloxane may be used.

[0236] In order to increase the degree of hydrophobization, it is preferable for the surface treatment agent to have an alkyl group with a large number of carbon atoms within its molecule. Specifically, it is preferable for the surface treatment agent to have an alkyl group with five or more carbon atoms within its molecule, and it is more preferable for it to have an alkyl group with six or more carbon atoms within its molecule. The alkyl group may be straight or branched, but it is preferable for it to be straight.

[0237] In addition, if the number of carbon atoms in the alkyl group within the molecule is too high, the rate at which the surface treatment agent can react with the functional groups on the surface of the inorganic particles is reduced due to the influence of the volume of the surface treatment agent molecule. For this reason, it is preferable that the number of carbon atoms in the alkyl group of the surface treatment agent be 20 or less, more preferable that it be 16 or less, and even more preferable that it be 12 or less.

[0238] When using inorganic particles alone as particles, it is also desirable to use inorganic particles that have been hydrophobized by another surface treatment agent. This is because if only inorganic particles that have been hydrophobized by the same surface treatment agent are used, aggregation may become excessive due to their similar properties.

[0239] When inorganic particles hydrophobized by another surface treatment agent are used in combination, the number of carbon atoms in the alkyl group of the surface treatment agent of one inorganic particle is preferably 4 or more, more preferably 6 or more, and the upper limit is preferably 20 or less, more preferably 16 or less, and more preferably 12 or less. Examples of the range of carbon atoms in the alkyl group of the surface treatment agent of one inorganic particle include 4 or more and 20 or less, 4 or more and 16 or less, 4 or more and 12 or less, 6 or more and 20 or less, 6 or more and 16 or less, and 6 or more and 12 or less. The number of carbon atoms in the alkyl group of the surface treatment agent of the other inorganic particle is preferably 3 or less, more preferably 2 or less, and more preferably 1.

[0240] The average particle size of the inorganic particles is preferably 3 nm or more at the lower limit, more preferably 5 nm or more, and even more preferably 8 nm or more at the upper limit, preferably 100 nm or less, more preferably 50 nm or less, and even more preferably 30 nm or less.

[0241] Examples of embodiments of the range of average particle diameter of inorganic particles include 3 nm or more and 100 nm or less, 3 nm or more and 50 nm or less, 3 nm or more and 30 nm or less, 5 nm or more and 100 nm or less, 5 nm or more and 50 nm or less, 5 nm or more and 30 nm or less, 8 nm or more and 100 nm or less, 8 nm or more and 50 nm or less, and 8 nm or more and 30 nm or less.

[0242] By setting the average particle size of the inorganic particles to the above range, it is possible to easily control the uneven shape caused by aggregates of inorganic particles. In addition, unless specifically stated otherwise, the average particle size of the inorganic particles in this specification refers to the average primary particle size. The average particle size of the inorganic particles can be measured, for example, by the laser scattering method.

[0243] Examples of metallic particles include particles consisting of the metal itself, such as gold and silver, and metal-coated particles in which the surface of organic particles is coated with metal. Since metallic particles have a heavy specific gravity and are difficult to float on the surface of the uneven layer, it is difficult to increase Sa. In addition, because metallic particles have low affinity with binder resin, the protruding parts of metallic particles protruding from the surface of the uneven layer are not coated with resin and form steep convex parts. For this reason, metallic particles have a tendency to increase Sa and Ssk to become very large.

[0244] From the above, it is desirable that the uneven surface layer substantially does not contain metallic particles.

[0245] The shape of the particles may include spherical, elliptical, or irregular shapes, but spherical particles are preferred. Spherical particles make it easier to suppress the irregularity of the irregular layer from becoming too steep, which makes it easier to suppress the excessive growth of Ssk.

[0246] The particle content is preferably 0.3 parts by mass or more, more preferably 0.4 parts by mass or more, and even more preferably 0.5 parts by mass or more, with respect to 100 parts by mass of binder resin, and preferably 12.0 parts by mass or less, more preferably 11.0 parts by mass or less, and even more preferably 10.0 parts by mass or less.

[0247] By making the particle content 0.3 parts by mass or more, it is easier to suppress the Sa of the uneven layer becoming too small and the Ssk becoming too large. In addition, by making the particle content 12.0 parts by mass or less, it is easier to suppress the Sa of the uneven layer becoming too large. In addition, if the particle is an organic particle, by making the particle content 12.0 parts by mass or less, it is easier to suppress the Ssk becoming too small.

[0248] Examples of embodiments for the range of particle content per 100 parts by mass of binder resin include 0.3 parts by mass or more and 12.0 parts by mass or less, 0.3 parts by mass or more and 11.0 parts by mass or less, 0.3 parts by mass or more and 10.0 parts by mass or less, 0.4 parts by mass or more and 12.0 parts by mass or less, 0.4 parts by mass or more and 11.0 parts by mass or less, 0.4 parts by mass or more and 10.0 parts by mass or less, 0.5 parts by mass or more and 12.0 parts by mass or less, 0.5 parts by mass or more and 11.0 parts by mass or less, and 0.5 parts by mass or more and 10.0 parts by mass or less.

[0249] The average film thickness of the uneven layer is preferably 0.5㎛ or more at the lower limit, more preferably 0.7㎛ or more, and even more preferably 1.0㎛ or more at the upper limit, preferably 7.0㎛ or less, more preferably 5.0㎛ or less, and even more preferably 3.0㎛ or less.

[0250] By making the average film thickness of the uneven layer 0.5㎛ or more, it is easier to suppress the Sa and Ssk of the uneven layer from becoming too large. In addition, by making the average film thickness of the uneven layer 7.0㎛ or less, it is easier to suppress the Sa and Ssk of the uneven layer from becoming too small.

[0251] Examples of embodiments for the range of the average film thickness of the uneven layer include 0.5㎛ or more and 7.0㎛ or less, 0.5㎛ or more and 5.0㎛ or less, 0.5㎛ or more and 3.0㎛ or less, 0.7㎛ or more and 7.0㎛ or less, 0.7㎛ or more and 5.0㎛ or less, 0.7㎛ or more and 3.0㎛ or less, 1.0㎛ or more and 7.0㎛ or less, 1.0㎛ or more and 5.0㎛ or less, and 1.0㎛ or more and 3.0㎛ or less.

[0252] The average film thickness of each layer constituting the optical laminate, such as the uneven surface layer and the antifouling layer, can be calculated by selecting 20 arbitrary locations in a cross-sectional image of the optical laminate taken with a scanning transmission electron microscope (STEM), for example, and calculating the average value. However, the 20 locations should be selected so that they are not skewed.

[0253] The acceleration voltage and magnification of the STEM can be set according to the layer of the measurement target. For example, in the case of an uneven layer, it is preferable to set the acceleration voltage of the STEM to 10 kV or more and 30 kV or less, and the magnification of the STEM to 1000 times or more and 7000 times or less.

[0254] The uneven surface layer may contain other additives to the extent that it does not impede the effects of the present disclosure. Examples of additives include leveling agents, ultraviolet absorbers, antioxidants, and light stabilizers.

[0255] The refractive index of the uneven layer is preferably 1.48 or higher at the lower limit, more preferably 1.50 or higher, and even more preferably 1.52 or higher at the upper limit, preferably 1.58 or lower, more preferably 1.54 or lower, and even more preferably 1.53 or lower. By setting the refractive index of the uneven layer to the above range and the refractive index of the antifouling layer to the range described below, it is easy to lower the visual reflectance Y value.

[0256] Examples of embodiments of the range of the refractive index of the uneven layer include 1.48 or more and 1.58 or less, 1.48 or more and 1.54 or less, 1.48 or more and 1.53 or less, 1.50 or more and 1.58 or less, 1.50 or more and 1.54 or less, 1.50 or more and 1.53 or less, 1.52 or more and 1.58 or less, 1.52 or more and 1.54 or less, and 1.52 or more and 1.53 or less.

[0257] "solvent"

[0258] In coating solutions for uneven surfaces, solvents are typically used to adjust viscosity or to dissolve or disperse each component.

[0259] Solvents may be examples of ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ethers such as dioxane and tetrahydrofuran; aliphatic hydrocarbons such as hexane; alicyclic hydrocarbons such as cyclohexane; aromatic hydrocarbons such as toluene and xylene; carbon halides such as dichloromethane and dichloroethane; esters such as methyl acetate, ethyl acetate, and butyl acetate; alcohols such as isopropanol, butanol, and cyclohexanol; cellosolves such as methyl cellosolve and ethyl cellosolve; glycol ethers such as propylene glycol monomethyl ether acetate; cellosolve acetates; sulfoxides such as dimethyl sulfoxide; amides such as dimethylformamide and dimethylacetamide; and mixtures thereof.

[0260] If the drying time required for the solvent in the coating solution for the uneven layer is too long, the Ssk may become too large due to excessive particle aggregation. Conversely, if the drying time required for the solvent in the coating solution for the uneven layer is too short, the Sa may become too small due to insufficient particle aggregation. For this reason, it is desirable to use a mixture of a solvent with a fast evaporation rate and a solvent with a slow evaporation rate in the coating solution for the uneven layer.

[0261] In this specification, a solvent with a fast evaporation rate refers to a solvent having an evaporation rate of 100 or more when the evaporation rate of butyl acetate is set to 100. Additionally, in this specification, a solvent with a slow evaporation rate refers to a solvent having an evaporation rate of less than 100 when the evaporation rate of butyl acetate is set to 100.

[0262] In the solvent for the coating solution for the uneven layer, the solvent with a fast evaporation rate is preferably 120 or higher, more preferably 130 or higher, and even more preferably 140 or higher, and the upper limit of the evaporation rate is preferably 400 or lower, more preferably 300 or lower, and even more preferably 220 or lower. Examples of solvents with a fast evaporation rate include methyl isobutyl ketone with an evaporation rate of 160, methyl ethyl ketone with an evaporation rate of 370, toluene with an evaporation rate of 200, and 2-propanol with an evaporation rate of 150.

[0263] Examples of embodiments of the range of evaporation rates of solvents with a fast evaporation rate include 120 or more and 400 or less, 120 or more and 300 or less, 120 or more and 220 or less, 130 or more and 400 or less, 130 or more and 300 or less, 130 or more and 220 or less, 140 or more and 400 or less, 140 or more and 300 or less, and 140 or more and 220 or less.

[0264] In the solvent for the coating solution for the uneven layer, the solvent with a slow evaporation rate is preferably 15 or higher, more preferably 20 or higher, and even more preferably 25 or higher, and the upper limit of the evaporation rate is preferably 90 or lower, more preferably 50 or lower, and even more preferably 35 or lower. Examples of solvents with a slow evaporation rate include cyclohexanone with an evaporation rate of 32 and propylene glycol monomethyl ether acetate with an evaporation rate of 44.

[0265] Examples of embodiments of the range of evaporation rates of solvents with slow evaporation rates include 15 or more and 90 or less, 15 or more and 50 or less, 15 or more and 35 or less, 20 or more and 90 or less, 20 or more and 50 or less, 20 or more and 35 or less, 25 or more and 90 or less, 25 or more and 50 or less, and 25 or more and 35 or less.

[0266] In the solvent of the coating solution for the uneven layer, the mass ratio of the solvent with a fast evaporation rate and the solvent with a slow evaporation rate is preferably 50:50 to 90:10, more preferably 50:50 to 80:20 or 60:40 to 90:10, and even more preferably 60:40 to 80:20.

[0267] In addition, regarding the solvent content in the coating solution for the uneven layer, it is preferable that the lower limit of the solid content concentration be 30 mass% or more, and more preferable that it be 35 mass% or more. In addition, regarding the solvent content in the coating solution for the uneven layer, it is preferable that the upper limit of the solid content concentration be 70 mass% or less, and more preferable that it be 45 mass% or less.

[0268] Examples of embodiments for the range of solvent content in the coating solution for the uneven layer include 30 mass% or more and 70 mass% or less, 30 mass% or more and 45 mass% or less, 35 mass% or more and 70 mass% or less, and 35 mass% or more and 45 mass% or less.

[0269] Antifouling layer

[0270] The antifouling layer is a layer located on the side opposite to the adhesion-easy layer of the uneven surface layer. It is preferable that the antifouling layer be formed in contact with the uneven surface layer. That is, it is preferable not to have another layer between the uneven surface layer and the antifouling layer.

[0271] In addition, it is desirable to position the antifouling layer so that it becomes the surface of the optical laminate.

[0272] Typically, when another component comes into contact with the surface of a laminate, significant stress is generated. Consequently, when another component comes into contact with the surface of a laminate having a functional layer, such as an easy-adhesion layer, on a polyester film with a high plane orientation ΔP, delamination occurs between the polyester film and the easy-adhesion layer due to the stress. The above stress is largely influenced by stress in the transverse direction.

[0273] However, when another member comes into contact with the surface of the antifouling layer of the optical laminate of the present disclosure, the other member slides due to the antifouling function of the antifouling layer, making it difficult to generate stress in the transverse direction. In addition, since irregularities are formed on the surface of the antifouling layer of the optical laminate of the present disclosure, which are formed by an irregularity layer satisfying Equation 2-1, the other member becomes difficult to adhere to the surface of the optical laminate due to the irregularities, making it difficult to generate stress. In this regard, the optical laminate of the present disclosure has good interlayer adhesion throughout the optical laminate, and can suppress the delamination of functional layers, such as an easy-to-adhere layer and an irregularity layer formed on a polyester film with a high plane orientation degree ΔP.

[0274] In addition, the optical laminate of the present disclosure forms an antifouling layer on an uneven surface layer satisfying Formula 2-1, thereby suppressing non-uniformity in thickness of the antifouling layer and further suppressing the occurrence of local defects in the optical laminate.

[0275] The antifouling layer can be formed, for example, by a coating solution for forming an antifouling layer comprising a binder resin composition and an antifouling agent. That is, an embodiment of the antifouling layer may include a binder resin and an antifouling agent.

[0276] The binder resin of the antifouling layer preferably comprises a cured product of a curable resin composition. Examples of cured products of the curable resin composition include cured products of a thermosetting resin composition and cured products of an ionizing radiation-curable resin composition. Among the cured products of the curable resin composition, a cured product of an ionizing radiation-curable resin composition is preferred to provide better mechanical strength.

[0277] The curable resin composition of the antifouling layer may be, for example, the curable resin composition exemplified in the uneven surface layer.

[0278] To ensure good antifouling properties, the resin composition forming the antifouling layer preferably comprises a resin composition containing fluorine atoms in its constituent units and a resin composition containing siloxane bonds in its constituent units. It is more preferable that these resin compositions have curability.

[0279] When using a resin composition containing fluorine atoms in its constituent units or a resin composition containing siloxane bonds in its constituent units, it is preferable to use it in combination with resin compositions other than these. As a resin composition other than a resin composition containing fluorine atoms in its constituent units and a resin composition containing siloxane bonds in its constituent units, a curable resin composition is preferred.

[0280] The ratio of the cured product of the curable resin composition to the total binder resin of the antifouling layer is preferably 60 mass% or more, more preferably 80 mass% or more, and even more preferably 90 mass% or more.

[0281] Examples of antifouling agents include fluorine leveling agents and silicone-based leveling agents.

[0282] In order to suppress bleed-out from the antifouling layer, it is desirable for the antifouling agent to have reactive groups capable of reacting with the binder resin composition. In other words, it is desirable for the antifouling agent to be immobilized in the binder resin composition within the antifouling layer.

[0283] In addition, to suppress bleed-out from the antifouling layer, a self-crosslinkable antifouling agent is also desirable.

[0284] The content of the antifouling agent in the antifouling layer is preferably 5 parts by mass or more at the lower limit, more preferably 10 parts by mass or more, and preferably 30 parts by mass or less at the upper limit, and more preferably 25 parts by mass or less, with respect to 100 parts by mass of the binder resin of the antifouling layer.

[0285] Examples of embodiments of the range of the content of the antifouling agent in the antifouling layer include, with respect to 100 parts by mass of the binder resin of the antifouling layer, 5 parts by mass or more and 30 parts by mass or less, 5 parts by mass or more and 25 parts by mass or less, 10 parts by mass or more and 30 parts by mass or less, and 10 parts by mass or more and 25 parts by mass or less.

[0286] The thickness of the antifouling layer is preferably 200 nm or less, more preferably 150 nm or less, and even more preferably 110 nm or less. By making the thickness of the antifouling layer 200 nm or less, it becomes easier to reflect the uneven shape of the uneven layer onto the surface of the antifouling layer, thereby making it easier to improve the adhesion of the optical laminate.

[0287] If the thickness of the antifouling layer is too thin, the in-plane uniformity of the antifouling properties is compromised, which may lead to a decrease in the adhesion of the optical laminate. Additionally, if the thickness of the antifouling layer is too thin, localized defects such as bright spots are prone to occur in the optical laminate. For this reason, it is preferable that the thickness of the antifouling layer be 50 nm or more, more preferable that it be 70 nm or more, and even more preferable that it be 90 nm or more.

[0288] Examples of embodiments for the range of thickness of the antifouling layer include 200 nm or less, 50 nm or more and 200 nm or less, 50 nm or more and 150 nm or less, 50 nm or more and 110 nm or less, 70 nm or more and 200 nm or less, 70 nm or more and 150 nm or less, 70 nm or more and 110 nm or less, 90 nm or more and 200 nm or less, 90 nm or more and 150 nm or less, and 90 nm or more and 110 nm or less.

[0289] As described below, when the antifouling layer is made to have a low refractive index, in order to lower the luminous reflectance Y value, the thickness of the antifouling layer is preferably 80 nm or more, more preferably 85 nm or more, and more preferably 90 nm, and the upper limit is preferably 120 nm or less, more preferably 110 nm or less, and more preferably 105 nm or less. At this time, the thickness of the antifouling layer is preferably larger than the average particle size of the particles included in the antifouling layer, such as hollow particles and non-hollow particles.

[0290] Examples of the thickness range for making the antifouling layer low refractive index include 80 nm or more and 120 nm or less, 80 nm or more and 110 nm or less, 80 nm or more and 105 nm or less, 85 nm or more and 120 nm or less, 85 nm or more and 110 nm or less, 85 nm or more and 105 nm or less, 90 nm or more and 120 nm or less, 90 nm or more and 110 nm or less, and 90 nm or more and 105 nm or less.

[0291] It is preferable that the contact angle of the surface of the antifouling layer with respect to pure water be 80 degrees or more, more preferable that it be 85 degrees or more, and even more preferable that it be 90 degrees or more. By making the contact angle 80 degrees or more, the slipperiness when another material contacts the surface of the optical laminate is improved, making it easier to improve the adhesion of the optical laminate.

[0292] If the pure contact angle of the antifouling layer is too large, the physical properties of the antifouling layer, such as hardness, may deteriorate as the ratio of the antifouling agent to the total solid content of the antifouling layer increases. For this reason, it is preferable that the contact angle be 130 degrees or less, and more preferable that it be 120 degrees or less.

[0293] Examples of the range of contact angles of the antifouling layer with respect to pure water include 80 degrees or more and 130 degrees or less, 80 degrees or more and 120 degrees or less, 85 degrees or more and 130 degrees or less, 85 degrees or more and 120 degrees or less, 90 degrees or more and 130 degrees or less, and 90 degrees or more and 120 degrees or less.

[0294] In this specification, the contact angle refers to the static contact angle measured by the θ / 2 method.

[0295] For pure water, general-purpose pure water can be used. Generally, pure water has a resistivity of 0.1 MΩ·cm or more and 15 MΩ·cm or less.

[0296] The antifouling layer may be made to have a low refractive index.

[0297] Specifically, the lower limit of the refractive index of the antifouling layer is preferably 1.10 or higher, more preferably 1.20 or higher, more preferably 1.26 or higher, more preferably 1.28 or higher, and more preferably 1.30 or higher; the upper limit is preferably 1.48 or lower, more preferably 1.45 or lower, more preferably 1.40 or lower, more preferably 1.38 or lower, and more preferably 1.32 or lower. By setting the refractive index of the antifouling layer to the above range, it is easier to lower the visual reflectance Y value.

[0298] As an embodiment of the range of the refractive index of the antifouling layer, it is 1.10 or more and 1.48 or less, 1.10 or more and 1.45 or less, 1.10 or more and 1.40 or less, 1.10 or more and 1.38 or less, 1.10 or more and 1.32 or less, 1.20 or more and 1.48 or less, 1.20 or more and 1.45 or less, 1.20 or more and 1.40 or less, 1.20 or more and 1.38 or less, 1.20 or more and 1.32 or less, 1.26 or more and 1.48 or less, 1.26 or more and 1.45 or less, 1.26 or more and 1.40 or less, 1.26 or more and 1.38 or less, 1.26 or more and 1.32 or less, 1.28 or more and 1.48 or less, 1.28 or more and 1.45 or less, 1.28 or more and 1.40 or less. Examples include 1.28 or more and 1.38 or less, 1.28 or more and 1.32 or less, 1.30 or more and 1.48 or less, 1.30 or more and 1.45 or less, 1.30 or more and 1.40 or less, 1.30 or more and 1.38 or less, and 1.30 or more and 1.32 or less.

[0299] When making the antifouling layer low in refractive index, it is desirable for the antifouling layer to contain particles.

[0300] It is preferable that the particles of the antifouling layer include hollow particles and non-hollow particles. That is, it is preferable that the low-refractive-index antifouling layer includes a binder resin, hollow particles, and non-hollow particles.

[0301] Hollow particles and non-hollow particles

[0302] The material of the hollow particles and non-hollow particles may be any of the inorganic compounds, such as silica and magnesium fluoride, or organic compounds; however, silica is preferred due to the low refractive index and strength. Below, regarding the hollow particles and non-hollow particles, the description will focus on hollow silica particles and non-hollow silica particles.

[0303] Hollow silica particles refer to particles that have an outer layer made of silica, with the interior of the particle surrounded by the outer layer being a cavity containing air. Hollow silica particles are particles in which, by containing air, the refractive index decreases in proportion to the occupancy of the gas relative to the original refractive index of silica. Non-hollow silica particles are particles that do not have a cavity like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles.

[0304] There are no specific limitations on the shape of hollow silica particles and non-hollow silica particles, and they may be approximately spherical shapes such as a perfect sphere, a spheroid, or a polyhedron that can approximate a sphere. Among these, considering scratch resistance, it is preferable to have a perfect sphere, a spheroid, or an approximately spherical shape.

[0305] Hollow silica particles play a role in lowering the refractive index of the entire antifouling layer by containing air. By using large-diameter hollow silica particles with a higher proportion of air, the refractive index of the antifouling layer can be further reduced. On the other hand, hollow silica particles tend to have lower mechanical strength. In particular, when large-diameter hollow silica particles with a high proportion of air are used, there is a tendency to easily reduce the scratch resistance of the antifouling layer.

[0306] Non-hollow silica particles play a role in improving the scratch resistance of the antifouling layer by being dispersed in the binder resin.

[0307] It is desirable to set the average particle size of the hollow silica particles and the average particle size of the non-hollow silica particles such that the hollow silica particles are close together and the non-hollow particles are placed between the hollow silica particles.

[0308] Specifically, the ratio of the average particle size of non-hollow silica particles to the average particle size of hollow silica particles, "average particle size of non-hollow silica particles / average particle size of hollow silica particles," is preferably 0.29 or less, and more preferably 0.27 or less. By setting the ratio of average particle sizes within the above range, hollow silica particles and non-hollow silica particles become more easily dispersed in the film thickness direction of the antifouling layer, making it easier to achieve good scratch resistance. Furthermore, the ratio of average particle sizes is preferably 0.05 or more, and more preferably 0.15 or more.

[0309] Examples of embodiments of the above-mentioned average particle size ratio range include 0.05 or more and 0.29 or less, 0.05 or more and 0.27 or less, 0.15 or more and 0.29 or less, and 0.15 or more and 0.27 or less.

[0310] Considering optical properties and mechanical strength, the lower limit of the average particle size of hollow silica particles is preferably 50 nm or more, more preferably 60 nm or more, and the upper limit is preferably 100 nm or less, more preferably 80 nm or less. Examples of the range of the average particle size of hollow silica particles include 50 nm or more and 100 nm or less, 50 nm or more and 80 nm or less, 60 nm or more and 100 nm or less, and 60 nm or more and 80 nm or less.

[0311] Considering dispersibility while preventing aggregation of non-hollow silica particles, the lower limit of the average particle size of the non-hollow silica particles is preferably 5 nm or more, more preferably 10 nm or more, and the upper limit is preferably 20 nm or less, more preferably 15 nm or less. Examples of the range of the average particle size of the non-hollow silica particles include 5 nm or more and 20 nm or less, 5 nm or more and 15 nm or less, 10 nm or more and 20 nm or less, and 10 nm or more and 15 nm or less.

[0312] It is preferable that the surfaces of hollow silica particles and non-hollow silica particles be coated with a silane coupling agent. As for the silane coupling agent, it is preferable that it have a (meth)acryloyl group or an epoxy group.

[0313] By surface treating silica particles with a silane coupling agent, the affinity between the silica particles and the binder resin is improved, making it difficult for the silica particles to aggregate. Consequently, the dispersion of the silica particles becomes more uniform. Furthermore, by improving the affinity between the silica particles and the binder resin through the silane coupling agent, the resistance increases when the wet antifouling layer formed on the convex portion of the uneven layer flows down toward the flat portion of the uneven layer. This makes it easier to suppress the excessive reduction in the film thickness of the antifouling layer on the convex portion of the uneven layer. Consequently, it is easier to suppress localized defects in the optical laminate.

[0314] As the content of hollow silica particles increases, the packing ratio of hollow silica particles in the binder resin increases, and the refractive index of the antifouling layer decreases. Furthermore, as the content of hollow silica particles increases, the viscosity of the coating solution for the antifouling layer increases. Consequently, the resistance increases when the wet antifouling layer formed on the convex portion of the uneven layer flows down toward the flat portion of the uneven layer, making it easier to suppress the excessive reduction of the film thickness of the antifouling layer on the convex portion of the uneven layer. For this reason, it is easier to suppress localized defects in the optical laminate. Accordingly, the content of hollow silica particles is preferably 100 parts by mass or more per 100 parts by mass of binder resin, and more preferably 130 parts by mass or more.

[0315] On the other hand, if the content of hollow silica particles is too high, the mechanical strength, such as the scratch resistance of the antifouling layer, tends to decrease. In addition, if the content of hollow silica particles is too high, the antifouling performance tends to decrease because the content of the antifouling agent decreases relatively. For this reason, it is preferable that the content of hollow silica particles be 300 parts by mass or less per 100 parts by mass of binder resin, and more preferable that it be 200 parts by mass or less.

[0316] Examples of embodiments of the range of hollow silica particle content per 100 parts by mass of binder resin include 100 parts by mass or more and 400 parts by mass or less, 100 parts by mass or more and 300 parts by mass or less, 130 parts by mass or more and 400 parts by mass or less, and 130 parts by mass or more and 300 parts by mass or less.

[0317] If the content of non-hollow silica particles is low, the presence of non-hollow silica particles on the surface of the antifouling layer may not affect the increase in hardness. Furthermore, as the content of non-hollow silica particles increases, the viscosity of the coating solution for the antifouling layer increases. Consequently, the resistance increases when the wet antifouling layer formed on the convex portion of the uneven layer flows down toward the flat portion of the uneven layer, making it easier to suppress the excessive reduction of the film thickness of the antifouling layer on the convex portion of the uneven layer. For this reason, it is easier to suppress localized defects in the optical laminate. Additionally, as the content of non-hollow silica particles increases, it is easier to minimize the influence of uneven shrinkage caused by the polymerization of the binder resin. Therefore, the content of non-hollow silica particles is preferably 10 parts by mass or more per 100 parts by mass of the binder resin, and more preferably 20 parts by mass or more.

[0318] On the other hand, if the content of non-hollow silica particles is too high, the content of the antifouling agent is relatively reduced, so the antifouling performance tends to decrease. For this reason, the content of non-hollow silica particles is preferably 150 parts by mass or less per 100 parts by mass of binder resin, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less.

[0319] Examples of embodiments for the range of the content of non-hollow silica particles per 100 parts by mass of binder resin include 10 parts by mass or more and 150 parts by mass or less, 10 parts by mass or more and 100 parts by mass or less, 10 parts by mass or more and 50 parts by mass or less, 20 parts by mass or more and 150 parts by mass or less, 20 parts by mass or more and 100 parts by mass or less, and 20 parts by mass or more and 50 parts by mass or less.

[0320] The antifouling layer may contain other additives to the extent that they do not impede the effects of the present disclosure. Examples of additives include ultraviolet absorbers, antioxidants, and light stabilizers.

[0321] "solvent"

[0322] In coating solutions for antifouling layers, solvents are typically used to adjust viscosity or to dissolve or disperse each component.

[0323] The solvent for the antifouling layer coating solution can be the same as that exemplified as the solvent for the uneven surface layer coating solution.

[0324] If the drying time required for the solvent in the antifouling coating solution is too long, the wet antifouling layer formed on the convex portion of the uneven layer may flow excessively toward the flat portion of the uneven layer, thereby causing the film thickness of the antifouling layer on the convex portion of the uneven layer to be excessively reduced. Furthermore, if the drying time required for the solvent in the antifouling coating solution is too short, the leveling properties of the antifouling layer may be insufficient. For this reason, it is desirable to use a mixture of a solvent with a fast evaporation rate and a solvent with a slow evaporation rate in the antifouling coating solution.

[0325] In the solvent of the coating liquid for the antifouling layer, the solvent with a fast evaporation rate is preferably 125 or higher, more preferably 130 or higher, and even more preferably 150 or higher, and the upper limit of the evaporation rate is preferably 450 or lower, more preferably 430 or lower, and even more preferably 400 or lower.

[0326] Examples of embodiments of the range of evaporation rates of solvents with a fast evaporation rate include 125 or more and 450 or less, 125 or more and 430 or less, 125 or more and 400 or less, 130 or more and 450 or less, 130 or more and 430 or less, 130 or more and 400 or less, 150 or more and 450 or less, 150 or more and 430 or less, and 150 or more and 400 or less.

[0327] In the solvent of the coating liquid for the antifouling layer, the solvent with a slow evaporation rate is preferably 20 or higher, more preferably 30 or higher, and even more preferably 40 or higher, and the upper limit of the evaporation rate is preferably 90 or lower, more preferably 60 or lower, and even more preferably 50 or lower.

[0328] Examples of embodiments of the range of evaporation rates of solvents with slow evaporation rates include 20 or more and 90 or less, 20 or more and 60 or less, 20 or more and 50 or less, 30 or more and 90 or less, 30 or more and 60 or less, 30 or more and 50 or less, 40 or more and 90 or less, 40 or more and 60 or less, and 40 or more and 50 or less.

[0329] In the solvent of the coating liquid for the antifouling layer, the mass ratio of the solvent with a fast evaporation rate and the solvent with a slow evaporation rate is preferably 50:50 to 90:10, more preferably 50:50 to 80:20 or 60:40 to 90:10, and even more preferably 60:40 to 80:20.

[0330] In addition, regarding the solvent content in the coating solution for the antifouling layer, it is preferable that the lower limit of the solid content concentration be 1 mass% or more, and more preferable that it be 2 mass% or more. In addition, regarding the solvent content in the coating solution for the antifouling layer, it is preferable that the upper limit of the solid content concentration be 10 mass% or less, and more preferable that it be 5 mass% or less.

[0331] Examples of embodiments for the range of solvent content in the coating solution for the antifouling layer include 1 mass% or more and 10 mass% or less, 1 mass% or more and 5 mass% or less, 2 mass% or more and 10 mass% or less, and 2 mass% or more and 5 mass% or less.

[0332] <Physical properties>

[0333] It is preferable that the optical laminate has a luminous reflectance Y value of 3.0% or less, measured at an angle of light incidence of 5 degrees from the side having the antifouling layer, and more preferable that it is 2.0% or less.

[0334] In addition, the lower limit of the luminous reflectance Y value is not specifically limited, but is usually about 0.5%.

[0335] In this specification, the luminous reflectance Y value refers to the luminous reflectance Y value of the CIE 1931 standard color system. The luminous reflectance Y value can be calculated using a spectrophotometer. When measuring luminous reflectance, it is preferable to bond a black plate to the back surface of the substrate. As an example of a spectrophotometer, the product name "UV-3600plus" of Shimadzu Seisakusho Co., Ltd. can be cited.

[0336] The luminous reflectance Y value, total light transmittance, and haze are the average values ​​measured at 10 locations.

[0337] The optical laminate preferably has an optical light transmittance of 50% or more according to JIS K7361-1:1997, more preferably 80% or more, and even more preferably 90% or more.

[0338] The total light transmittance and the haze described below are measured with the light incident surface facing the polyester film. The total light transmittance and the haze described below can be measured, for example, with a haze meter manufactured by Murakami Shikisai Kijutsu Genkyujo (Product No.: HM-150).

[0339] The optical laminate preferably has a haze conforming to JIS K7136:2000, with a lower limit of 0.3% or more, more preferably 0.4% or more, even more preferably 0.5% or more, an upper limit of 10% or less, more preferably 7% or less, and even more preferably 5% or less.

[0340] Examples of embodiments of the haze range of the optical laminate include 0.3% or more and 10% or less, 0.3% or more and 7% or less, 0.3% or more and 5% or less, 0.4% or more and 10% or less, 0.4% or more and 7% or less, 0.4% or more and 5% or less, 0.5% or more and 10% or less, 0.5% or more and 7% or less, and 0.5% or more and 5% or less.

[0341] <Size, shape, etc.>

[0342] The optical laminate may be in the form of a single-wafer cut to a predetermined size, or in the form of a roll wound from a long sheet. The size of the single-wafer is not particularly limited, but the maximum diameter is approximately 2 inches or more and 500 inches or less. "Maximum diameter" refers to the maximum length when any two points of the optical laminate are connected. For example, if the optical laminate is rectangular, the diagonal of the rectangle becomes the maximum diameter. If the optical laminate is circular, the diameter of the circle becomes the maximum diameter.

[0343] The width and length of the roll shape are not particularly limited, but generally, the width is 500 mm or more and 8000 mm or less, and the length is 100 m or more and 10000 m or less. The optical laminate in the roll shape can be cut into a single-wafer shape to fit the size of an image display device, etc. When cutting, it is preferable to exclude the roll ends where the physical properties are unstable.

[0344] The shape of the sheet is not particularly limited and, for example, may be a polygon such as a triangle, square, or pentagon, may be circular, or may be a random irregular shape. More specifically, when the optical laminate is square in shape, the aspect ratio is not particularly limited as long as there is no problem with it as a display screen. For example, width:height ratios of 1:1, 4:3, 16:10, 16:9, 2:1, 5:4, 11:8, etc. can be given.

[0345] [Polarizing plate]

[0346] The polarizing plate of the present disclosure is a polarizing plate having a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is an optical laminate of the present disclosure as described above, and the optical laminate is arranged such that the surface of the antifouling layer faces the opposite side of the polarizer.

[0347] Polarizer

[0348] Examples of polarizers include sheet-type polarizers such as polyvinyl alcohol films dyed and stretched with iodine, polyvinyl formal films, polyvinyl acetal films, and ethylene-vinyl acetate copolymer saponification films; wire grid-type polarizers composed of a plurality of metal wires arranged in parallel; coating-type polarizers coated with lyotropic liquid crystals or dichromatic guest-host materials; and multilayer thin-film polarizers. These polarizers may also be reflective polarizers equipped with the function of reflecting polarization components that are not transmitted.

[0349] Transparent protective plate

[0350] A first transparent protective plate is disposed on one side of the polarizer, and a second transparent protective plate is disposed on the other side. At least one of the first transparent protective plate and the second transparent protective plate is the optical laminate of the present disclosure described above.

[0351] Examples of the first and second transparent protective plates other than the optical laminate include plastic films and glass. Examples of plastic films include polyester films, polycarbonate films, cycloolefin polymer films, and acrylic films, and stretched films of these are preferred to ensure good mechanical strength. Examples of glass include alkali glass, glass nitride, soda-lime glass, borosilicate glass, and lead glass. In addition, it is preferable for the glass serving as the transparent protective plate protecting the polarizer to be used in combination with other components of the image display device. For example, it is preferable to use the glass substrate of the liquid crystal display element and the transparent protective plate protecting the polarizer together.

[0352] In addition, it is preferable to bond the polarizer and the transparent protective plate using an adhesive. A general-purpose adhesive can be used, and a PVA-based adhesive is preferred.

[0353] In the polarizing plate of the present disclosure, both the first transparent protective plate and the second transparent protective plate may be the optical laminate of the present disclosure described above, but it is preferable that one of the first transparent protective plate and the second transparent protective plate is the optical laminate of the present disclosure described above. Furthermore, when the polarizing plate of the present disclosure is used as a polarizing plate positioned on the light-emitting surface side of a display element, it is preferable that the transparent protective plate on the light-emitting surface side of the polarizer is the optical laminate of the present disclosure described above. On the other hand, when the polarizing plate of the present disclosure is used as a polarizing plate positioned on the side opposite to the light-emitting surface of a display element, it is preferable that the transparent protective plate on the side opposite to the light-emitting surface of the polarizer is the optical laminate of the present disclosure described above.

[0354] [Surface plate for image display device]

[0355] The surface plate for an image display device of the present disclosure is a surface plate for an image display device having an optical laminate bonded to a resin plate or a glass plate, wherein the optical laminate is the optical laminate of the present disclosure described above, and the optical laminate is arranged such that the surface of the antifouling layer faces the opposite side to the resin plate or the glass plate.

[0356] It is preferable to position the surface plate for the image display device such that the side on which the optical laminate is bonded faces the surface side. In other words, it is preferable to position the surface plate for the image display device such that the side on which the optical laminate is bonded faces the side opposite to the display element.

[0357] As for the resin plate or glass plate, a resin plate or glass plate that is commonly used as a surface plate for an image display device may be used.

[0358] The thickness of the resin plate or glass plate is preferably 10 μm or more to ensure good strength. The upper limit of the thickness of the resin plate or glass plate is usually 5000 μm or less, but in recent years, as thinning of image display devices is desirable, it is preferable to have a thickness of 1000 μm or less, more preferable to have a thickness of 500 μm or less, and even more preferable to have a thickness of 100 μm or less.

[0359] Examples of embodiments for the thickness range of the resin plate or glass plate include 10㎛ or more and 5000㎛ or less, 10㎛ or more and 1000㎛ or less, 10㎛ or more and 500㎛ or less, and 10㎛ or more and 100㎛ or less.

[0360] [Image display device]

[0361] The image display device of the present disclosure is arranged on a display element such that the antifouling layer side of the optical laminate of the present disclosure described above faces opposite to the display element, and the optical laminate is also arranged on a surface.

[0362] Examples of display elements include EL display elements such as liquid crystal display elements, organic EL display elements and inorganic EL display elements, plasma display elements, etc. Furthermore, LED display elements such as mini LED display elements and micro LED display elements can be cited. These display elements may have a touch panel function inside the display element.

[0363] Examples of liquid crystal display methods for liquid crystal display elements include IPS, VA, multi-domain, OCB, STN, and TSTN methods. When the display element is a liquid crystal display element, a backlight is required. The backlight is placed on the side opposite to the side having the optical stack of the liquid crystal display element. Examples of backlights include backlights using quantum dots and backlights using white light-emitting diodes.

[0364] The image display device may be a foldable image display device or a rollable image display device. Additionally, the image display device may be an image display device equipped with a touch panel.

[0365] Examples

[0366] The present disclosure will be explained in detail below with reference to examples and comparative examples. Furthermore, the present disclosure is not limited to the forms described in the examples.

[0367] 1. Evaluation, Measurement

[0368] For the optical laminates obtained in Examples 1 to 20 and Comparative Examples 1 to 21, measurements and evaluations as described in 1-1 to 1-6 below were performed. The results are shown in Tables 1 to 4. In addition, unless otherwise noted, the atmosphere during each measurement and evaluation was set to a temperature of 23±5℃ and a relative humidity of 40% or more and 65% or less, and before the start of each measurement and evaluation, the target sample was exposed to the above atmosphere for at least 30 minutes, and then the measurement and evaluation were performed.

[0369] 1-1. Measurement of Sa and Ssk

[0370] In the examples and comparative examples, the surface shape of the uneven layer was measured after forming an easy-to-adhesion layer and an uneven layer on a polyester film (PET film) and before forming an antifouling layer. From the measured surface shape, Sa, Ssk, and "A" in Equation 2-1 were calculated. For the measurement of the surface shape, a laser microscope (Olympus product name "LEXT OLS4000") was used, and measurements and analyses were performed under the following conditions. The Sa and Ssk measured by the laser microscope conform to ISO 25178:2012. The results are shown in Tables 1 to 4.

[0371] <Measurement Conditions>

[0372] Objective: MPLAPONLEXT50 (50x lens)

[0373] Zoom: ×1

[0374] Image size (pixels): 1024×1024

[0375] Image size: 258㎛×259㎛

[0376] Cutoff value: Not set

[0377] <Interpretation Conditions>

[0378] Interpretation Mode: Face

[0379] Output type: Roughness

[0380] 1-2. Adhesion

[0381] A 100-square grid-shaped cut was formed by inserting the cutter blade from the antifouling layer side of the optical laminate of the example and comparative example (number of cuts: 11 cutting lines in the vertical and horizontal directions, cut interval: 1 mm). The cutter blade used was NT Corporation's product number "BA-52P". Subsequently, an adhesive tape (Nichiban Co., Ltd., product name "Cellophane Tape" (registered trademark)) was applied to the surface of the optical laminate where the grid was formed, and then a peel test was performed in accordance with the cross-cut method specified in JIS K5600-5-6:1999 by peeling off the adhesive tape. The adhesion of the optical laminate of the example and comparative example was evaluated according to the following evaluation criteria.

[0382] <Evaluation Criteria>

[0383] A: The number of peeled cells is 0, and there is no shortage of any cells.

[0384] B: Although the number of peeled compartments is 0, there are places where some compartments are missing due to cutting or other factors.

[0385] C: The number of peeled cells is 1 or more.

[0386] 1-3. Bright spots

[0387] The optical laminates of the examples and comparative examples were installed on a horizontal stand with the antifouling layer side facing upward, and the presence or absence of bright spots was visually evaluated from various angles in which the reflected light from the fluorescent lamp was observed under a bright environment. The evaluation was performed from a straight distance of approximately 50 cm above the sample. The conditions of the bright environment were set so that the illuminance on the sample was between 500 lux and 1000 lux. An Hf32 type linear triphosphor cool white fluorescent lamp was used as the lighting. The position of the lighting was set at a height of 2 m vertically above the horizontal stand.

[0388] A total of 20 subjects, consisting of 5 from each age group from their 20s to 50s, evaluated the test by assigning 3 points for no concern with the bright spot, 2 points for neither, and 1 point for concern with the bright spot. The average score of the 20 evaluations was calculated, and a rank was assigned according to the following criteria.

[0389] <Evaluation Criteria>

[0390] A: Average score is 2.5 or higher

[0391] B: Average score is 2.0 or higher and less than 2.5

[0392] C: Average score less than 2.0

[0393] 1-4. Contact Angle

[0394] Using a contact angle meter (manufactured by Kyowa Kaimen Kagaku, Product No.: DM-300), 1.0 μL of pure water was dropped onto the surface of the antifouling layer side of the optical laminates of the examples and comparative examples, and the static contact angle after 10 seconds of deposition was measured according to the θ / 2 method. Three measurements were taken, and the average value was taken as the contact angle of each example and comparative example.

[0395] 1-5. Luminous Reflectance Y Value (Reflectance)

[0396] A 5 cm × 5 cm sample was produced by bonding a black plate (Curare, product name: Como Glass DFA2CG 502K (black) series, thickness 2 mm) to the substrate side of the optical laminate of the example and comparative example, with a transparent adhesive layer (Panax, product name: PANA Clean PD-S1) with a thickness of 25 μm.

[0397] When the direction perpendicular to the surface of the antifouling layer of the optical laminate is set to 0 degrees, light is incident on the sample from a direction of 5 degrees, and the luminous reflectance Y value, which is the reflectance of the sample, is measured based on the specular reflection of the incident light.

[0398] Reflectance was determined by measuring 5-degree specular reflection light using a spectroscopic reflectance meter (Nihon Bunko Co., Ltd., product name: V-7100) under conditions of a viewing angle of 2 degrees, a C light source, and a wavelength range of 380 nm to 780 nm, and then calculating the value representing the luminous reflectance, which is converted into brightness perceived by the human eye using software (JASCO Spectrum Manager Ver2.0), as the reflectance. Measurements were taken at 10 locations within the sample, and the average value of the 10 locations was taken as the reflectance for each example and comparative example. A mask with dimensions of 5 mm × 10 mm was used during measurement. Accordingly, the size of the measurement spot for reflectance at an incident angle of 5 degrees is 50.2 mm².

[0399] 1-6. Total Light Transmittance (Tt) and Haze (Hz)

[0400] Using a haze meter (HM-150, manufactured by Kijutsu Genkyujo, Murakami), the total light transmittance according to JIS K7361-1:1997 and the haze according to JIS K7136:2000 were measured for the optical laminates of the examples and comparative examples. The light incident surface was the polyester film side.

[0401] 2. Synthesis of Compound A (Urethane Acrylate Oligomer)

[0402] After introducing air gas into a reaction vessel equipped with a stirrer, thermometer, cooling tube, and nitrogen gas inlet tube, 10.0 parts by mass of 1,3-butanediol, 10.0 parts by mass of 1,4-butanediol, 0.1 parts by mass of p-methoxyphenol, 0.1 parts by mass of dibutyltin dilaurate, and 100.0 parts by mass of methyl ethyl ketone were added, and the temperature was raised to 50°C while stirring under a nitrogen stream. Meanwhile, 50.3 parts by mass of isophorone diisocyanate were added to a dropping vessel and uniformly dropped into the reaction vessel over a period of 1 hour. At that time, the temperature of the reaction vessel was maintained at 50±3°C. After maintaining the temperature for 1 hour while stirring, 0.1 parts by mass of p-methoxyphenol and 0.1 parts by mass of dibutyltin dilaurate were additionally added, and the temperature was raised to 60°C while stirring under a nitrogen stream. After that, 176.0 parts by mass of a mixture of pentaerythritol triacrylate and pentaerythritol tetraacrylate in a mass ratio of 80:20, which had been added to the dropping container, was uniformly dropped into a reaction vessel while stirring for 1 hour.

[0403] After the dropping process was completed, the dropping vessel was washed with 120.0 parts by mass of methyl ethyl ketone, and the solution after washing was transferred directly into the reaction vessel. After holding the temperature for 2 hours while stirring again, the temperature was raised to 75°C. Subsequently, stirring and holding were continued at 75±3°C until the peak derived from isocyanato in the infrared absorption spectrum disappeared. The peak derived from isocyanato disappeared after approximately 4 to 6 hours. After confirming the disappearance of this peak, the temperature was lowered to 60°C, 7.0 parts by mass of methanol was added, and the temperature was held at 60±3°C for 30 minutes. Then, 120.8 parts by mass of methyl ethyl ketone were added to obtain a transparent resin solution. Finally, the solvent was removed using an evaporator to obtain compound A, a urethane acrylate oligomer. The weight average molecular weight of the obtained compound A was 2000.

[0404] 3. Preparation of the coating solution

[0405] (1) Coating solution for uneven surface layer 1

[0406] Coating solution 1 for an uneven layer was prepared by diluting the following materials with a mixed solvent of methyl isobutyl ketone and methyl ethyl ketone in a mass ratio of 35:65 so that the solid content concentration was 40 mass%.

[0407] <Materials of Coating Solution 1 for Uneven Surface Layer>

[0408] · Pentaerythritol triacrylate: 56 parts by mass

[0409] (Nippon Kayaku Co., Ltd., Product name "PET-30", Solid content 100 mass%)

[0410] · UV-curing acrylate-containing composition: 44 parts by mass

[0411] (Daiichi Kogyo Co., Ltd. Pharmacist, Product Name "New Frontier R-1403MB", Solid Content 80% by mass)

[0412] · Photopolymerization initiator: 3 parts by mass

[0413] (IGM Resins BV, Product Name "Omnirad 184")

[0414] · Leveling agent: 3 parts by mass

[0415] (DIC, Product Name "MegaPac F-568", Solid Content 5% by Mass)

[0416] (2) Coating solution for uneven surface layer 2

[0417] Coating solution 2 for an uneven layer was prepared by diluting the following materials with a mixed solvent of toluene, 2-propanol, and cyclohexanone in a mass ratio of 60:10:30 so that the solid content concentration was 40 mass%.

[0418] <Materials of Coating Solution 2 for Uneven Layers>

[0419] · Pentaerythritol tetraacrylate: 45 parts by mass

[0420] (Product Name: PETA, Daicel & Cytec)

[0421] · Urethane acrylate oligomer: 55 parts by mass

[0422] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0423] · Photopolymerization initiator: 3 parts by mass

[0424] (IGM Resins BV, Product Name "Esacure 1")

[0425] · Organic particles: 0.5 parts by mass

[0426] (Acrylic beads, average particle size 2.2㎛, refractive index 1.559, coefficient of variation: 10.4%)

[0427] · Leveling agent: 0.5 parts by mass

[0428] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0429] (3) Coating solution for uneven surface layer 3

[0430] Coating solution 3 for an uneven layer was prepared by diluting the following materials with a mixed solvent of toluene, 2-propanol, and cyclohexanone in a mass ratio of 60:10:30 so that the solid content concentration was 40 mass%.

[0431] <Materials of Coating Solution 3 for Uneven Surface Layer>

[0432] · Pentaerythritol tetraacrylate: 45 parts by mass

[0433] (Product Name: PETA, Daicel & Cytec)

[0434] · Urethane acrylate oligomer: 55 parts by mass

[0435] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0436] · Photopolymerization initiator: 3 parts by mass

[0437] (IGM Resins BV, Product Name "Esacure 1")

[0438] · Organic particles: 0.6 parts by mass

[0439] (Acrylic beads, average particle size 2.2㎛, refractive index 1.559, coefficient of variation: 10.4%)

[0440] · Fumed silica: 1 part by mass

[0441] (Octylsilane treatment, average particle size 12 nm, Nippon Aerosil yarn)

[0442] · Leveling agent: 0.5 parts by mass

[0443] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0444] (4) Coating solution for uneven surface layer 4

[0445] The following materials were diluted with a mixed solvent of toluene, 2-propanol, and cyclohexanone in a mass ratio of 60:10:30 to obtain a solid content concentration of 40 mass%, thereby preparing a coating solution 4 for an uneven layer.

[0446] <Materials of Coating Solution 4 for Uneven Layers>

[0447] · Pentaerythritol tetraacrylate: 45 parts by mass

[0448] (Product Name: PETA, Daicel & Cytec)

[0449] · Urethane acrylate oligomer: 55 parts by mass

[0450] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0451] · Photopolymerization initiator: 3 parts by mass

[0452] (IGM Resins BV, Product Name "Esacure 1")

[0453] · Fumed silica: 0.5 parts by mass

[0454] (Octylsilane treatment, average particle size 12 nm, Nippon Aerosil yarn)

[0455] · Fumed silica: 0.2 parts by mass

[0456] (Methylsilane treatment, average particle size 12 nm, Nippon Aerosil yarn)

[0457] · Leveling agent: 0.5 parts by mass

[0458] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0459] (5) Coating solution for uneven surface layer 5

[0460] The following materials were diluted with a mixed solvent of toluene, 2-propanol, and cyclohexanone in a mass ratio of 60:10:30 to obtain a solid content concentration of 40 mass%, thereby preparing a coating solution 5 for an uneven layer.

[0461] <Materials of Coating Solution 5 for Uneven Layers>

[0462] · Pentaerythritol tetraacrylate: 45 parts by mass

[0463] (Product Name: PETA, Daicel & Cytec)

[0464] · Urethane acrylate oligomer: 55 parts by mass

[0465] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0466] · Photopolymerization initiator: 3 parts by mass

[0467] (IGM Resins BV, Product Name "Esacure 1")

[0468] · Organic particles: 3 parts by mass

[0469] (Acrylic beads, average particle size 2.3㎛, refractive index 1.559, coefficient of variation: 10.2%)

[0470] · Fumed silica: 1 part by mass

[0471] (Octylsilane treatment, average particle size 12 nm, Nippon Aerosil yarn)

[0472] · Leveling agent: 0.5 parts by mass

[0473] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0474] (6) Coating solution for uneven surface layer 6

[0475] The following materials were diluted with a mixed solvent of toluene, 2-propanol, and cyclohexanone in a mass ratio of 60:10:30 to obtain a solid content concentration of 40 mass%, thereby preparing a coating solution 6 for an uneven layer.

[0476] <Materials of Coating Solution 6 for Uneven Layers>

[0477] · Pentaerythritol tetraacrylate: 45 parts by mass

[0478] (Product Name: PETA, Daicel & Cytec)

[0479] · Urethane acrylate oligomer: 55 parts by mass

[0480] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0481] · Photopolymerization initiator: 3 parts by mass

[0482] (IGM Resins BV, Product Name "Esacure 1")

[0483] · Organic particles: 10 parts by mass

[0484] (Acrylic beads, average particle size 3.0㎛, refractive index 1.559, coefficient of variation: 9.8%)

[0485] · Leveling agent: 0.5 parts by mass

[0486] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0487] (7) Coating solution for uneven surface layer 7

[0488] The following materials were diluted with a mixed solvent of toluene, 2-propanol, and cyclohexanone in a mass ratio of 60:10:30 to obtain a solid content concentration of 40 mass%, thereby preparing a coating solution 7 for an uneven layer.

[0489] <Materials of Coating Solution 7 for Uneven Surface Layers>

[0490] · Pentaerythritol tetraacrylate: 45 parts by mass

[0491] (Product Name: PETA, Daicel & Cytec)

[0492] · Urethane acrylate oligomer: 55 parts by mass

[0493] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0494] · Photopolymerization initiator: 3 parts by mass

[0495] (IGM Resins BV, Product Name "Esacure 1")

[0496] · Organic particles: 15 parts by mass

[0497] (Acrylic beads, average particle size 3.6㎛, refractive index 1.559, coefficient of variation: 10.5%)

[0498] · Metal coating particles: 0.5 parts by mass

[0499] (Nickel-coated acrylic beads, average particle size 4.5㎛)

[0500] · Leveling agent: 0.5 parts by mass

[0501] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0502] (8) Coating solution for uneven surface layer 8

[0503] Coating solution 8 for an uneven layer was prepared by diluting the following materials with a mixed solvent of 4-methyl-2-pentanone and 2-propanol in a mass ratio of 70:30 so that the solid content concentration was 40 mass%.

[0504] <Materials of Coating Solution 8 for Uneven Surface Layers>

[0505] · Pentaerythritol triacrylate: 100 parts by mass

[0506] (Product Name: PET-30, Nippon Kayakusa)

[0507] · Photopolymerization initiator: 3 parts by mass

[0508] (IGM Resins BV, Product Name "Esacure 1")

[0509] · Metal coating particles: 0.6 parts by mass

[0510] (Nickel-coated acrylic beads, average particle size 4.5㎛)

[0511] · Leveling agent: 0.5 parts by mass

[0512] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0513] (9) Coating solution for uneven surface layer 9

[0514] The following materials were diluted with a mixed solvent of 4-methyl-2-pentanone and 2-propanol in a mass ratio of 70:30 to obtain a solid content concentration of 40 mass%, thereby preparing a coating solution 9 for an uneven layer.

[0515] <Materials of Coating Solution 9 for Uneven Surface Layers>

[0516] · Pentaerythritol triacrylate: 100 parts by mass

[0517] (Product Name: PET-30, Nippon Kayakusa)

[0518] · Photopolymerization initiator: 3 parts by mass

[0519] (IGM Resins BV, Product Name "Esacure 1")

[0520] · Leveling agent: 0.5 parts by mass

[0521] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0522] (10) Coating solution for uneven surface layer 10

[0523] The following materials were diluted with a mixed solvent of toluene and cyclohexanone in a mass ratio of 70:30 to obtain a solid content concentration of 40 mass%, thereby preparing a coating solution 10 for an uneven layer.

[0524] <Materials of Coating Solution 10 for Uneven Layers>

[0525] · Pentaerythritol tetraacrylate: 45 parts by mass

[0526] (Product Name: PETA, Daicel & Cytec)

[0527] · Urethane acrylate oligomer: 55 parts by mass

[0528] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0529] · Photopolymerization initiator: 3 parts by mass

[0530] (IGM Resins BV, Product Name "Esacure 1")

[0531] · Organic particles: 15 parts by mass

[0532] (Acrylic beads, average particle size 3.6㎛, refractive index 1.559, coefficient of variation: 10.5%)

[0533] · Leveling agent: 0.5 parts by mass

[0534] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0535] (11) Coating solution for uneven surface layer 11

[0536] The following materials were diluted with a mixed solvent of toluene and cyclohexanone in a mass ratio of 70:30 to obtain a solid content concentration of 40 mass% to prepare a coating solution 11 for an uneven layer.

[0537] <Materials of Coating Solution 11 for Uneven Layers>

[0538] · Pentaerythritol tetraacrylate: 45 parts by mass

[0539] (Product Name: PETA, Daicel & Cytec)

[0540] · Urethane acrylate oligomer: 55 parts by mass

[0541] (Mitsubishi Chemical Corporation, Product name "UV-1700B", Solid content 100 mass%)

[0542] · Photopolymerization initiator: 3 parts by mass

[0543] (IGM Resins BV, Product Name "Esacure 1")

[0544] · Organic particles: 0.5 parts by mass

[0545] (Acrylic beads, average particle size 3.6㎛, refractive index 1.559, coefficient of variation: 10.5%)

[0546] · Leveling agent: 0.5 parts by mass

[0547] (Dainichi Seika Kogyo Co., Ltd., Product Name "Seika Beam 10-28 (TL)", Solid Content 10 mass%)

[0548] (12) Coating solution for antifouling layer

[0549] The following materials were diluted with a mixed solvent of methyl isobutyl ketone, methyl ethyl ketone, and propylene glycol monomethyl ether acetate in a mass ratio of 40:30:30 to obtain a solid content concentration of 2.5 mass%, and a coating solution for an antifouling layer was prepared.

[0550] <Materials for Antifouling Coating Solution>

[0551] · The above compound (A): 15 parts by mass

[0552] (Urethane acrylate oligomer, solid content 100 mass%)

[0553] · Fluorine-containing resin composition: 850 parts by mass

[0554] (Arakawa Kagaku Kogyo Co., Ltd., Product Name "TU-2362", Solid Content 10% by Mass)

[0555] · Photopolymerization initiator: 5 parts by mass

[0556] (IGM Resins BV, Product Name "Omnirad 127")

[0557] · Hollow silica particles: 100 parts by mass

[0558] (Average particle size 60 nm, refractive index 1.212)

[0559] · Solid silica particles: 25 parts by mass

[0560] (Average particle size 15 nm)

[0561] · Fluorine-based leveling agent: 100 parts by mass

[0562] (Made by Shin-Etsu Silicone, Product name "X-71-1203M", Solid content 20 mass%)

[0563] 4. Fabrication and preparation of PET film, and measurement of in-plane phase difference of PET film

[0564] As polyester films of the examples and comparative examples, the following PET films 1 to 4 were produced, and the following PET film 5 was prepared.

[0565] In addition, using Otsuka Denshi Corporation’s product name “RETS-100”, the nx, ny, and nz, and the in-plane phase difference (Re) of each PET film were measured. The Δn(nx-ny), ΔP, and in-plane phase difference (Re) of each PET film are shown in Table 5.

[0566] 4-1. PET Film 1

[0567] <Production of Raw Material (PET (A))>

[0568] When the esterification reaction can was heated to 200°C, 86.5 parts by mass of terephthalic acid and 64.5 parts by mass of ethylene glycol were added, and while stirring, 0.020 parts by mass of antimony trioxide, 0.061 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were added as catalysts. Subsequently, the pressure was increased to carry out a pressure esterification reaction under conditions of a gauge pressure of 0.34 MPa and 240°C, after which the esterification reaction can was returned to atmospheric pressure and 0.014 parts by mass of phosphoric acid was added. Additionally, the temperature was increased to 260°C over 15 minutes and 0.012 parts by mass of trimethyl phosphate were added. Subsequently, after 15 minutes, a dispersion treatment was performed in a high-pressure disperser, and an ethylene glycol slurry of silica particles with an average particle size of 2.5 μm was added as a particle content, containing 0.1 mass% of sodium tripolyphosphate aqueous solution as sodium atoms relative to the silica particles, cutting off 35% of the agglomerates by centrifugation, and filtering with a metal filter with a mesh size of 5 μm. After 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reaction can, and a polycondensation reaction was carried out under reduced pressure at 280°C.

[0569] After the polycondensation reaction was completed, the product was filtered using a Naslon filter with a 95% cut diameter of 5 μm, extruded from a nozzle in a strand shape, cooled and solidified using cooling water that had been filtered beforehand with a filter with a hole diameter of 1 μm or less, and cut into a pellet shape. The intrinsic viscosity of the obtained polyethylene terephthalate resin (A) was 0.64 dl / g, the oligomer content was 0.96 mass%, and it substantially contained no inert particles or internal precipitated particles. Additionally, "polyethylene terephthalate resin (A)" is sometimes abbreviated as "PET (A)".

[0570] <Production of Raw Material (PET (B))>

[0571] In the manufacture of the above PET (A), a polyethylene terephthalate resin (B) with an intrinsic viscosity of 0.62 dl / g was obtained without adding silica particles. Additionally, "polyethylene terephthalate resin (B)" is sometimes abbreviated as "PET (B)".

[0572] <PET 필름 1의 제작>

[0573] 100 parts by mass of PET (B) resin pellets with an intrinsic viscosity of 0.62 dl / g were dried under reduced pressure at 1 Torr for 6 hours at 135°C and then supplied to an extruder (2) for intermediate layer II. Additionally, PET (A) and PET (B) were mixed and adjusted so that the silica particle content was 0.10 mass%, dried by a conventional method, and then supplied to an extruder (1) for outer layer I and outer layer III. The silica particles were the silica particles contained in PET (A). The PET supplied to extruders (1 and 2) was melted at 288°C. The melted polymers were each filtered through a stainless steel sintered filter material, laminated using a 2-type 3-layer combined block, extruded from a die in the shape of a sheet, and then wound onto a casting drum with a surface temperature of 30°C using an electrostatic casting method and cooled to solidify to produce an unoriented film. At this time, the discharge volume of each extruder was adjusted so that the ratio of the thicknesses of the I layer, II layer, and III layer was 5:90:5. The filter material of the above stainless steel sintered body is a filter material with "nominal filtration precision; 95% cut of 10㎛ particles".

[0574] This unoriented film was heated to 100°C using a heated roll group and an infrared heater, and then stretched 3.0 times in the longitudinal direction using a roll group with a peripheral speed difference to obtain a uniaxially oriented PET film.

[0575] Next, the uniaxially stretched film was guided to a tenter stretcher, and while gripping the end of the film with a clip, it was guided into a hot air zone at a temperature of 140°C and stretched 3.2 times in the width direction. Then, while maintaining the width stretched in the width direction, it was guided into a hot air zone at a temperature of 210°C and stretched 1.1 times in the width direction in this hot air zone. Additionally, after performing heat treatment for about 5 seconds in the hot air zone at a temperature of 210°C, a relaxation treatment of 3% in the width direction was performed to obtain a biaxially stretched PET film (PET film 1) with a film thickness of about 40 μm.

[0576] 4-2. PET Film 2

[0577] A biaxially stretched PET film 2 was obtained in the same manner as PET film 1, except that the lengthwise stretching ratio was changed to 3.5 times, the first step stretching ratio in the widthwise direction to 3.6 times, and the second step stretching ratio in the widthwise direction to 1.2 times.

[0578] 4-3. PET Film 3

[0579] A biaxially stretched PET film 3 was obtained in the same manner as PET film 1, except that the lengthwise stretching ratio was changed to 3.9 times, the first stage of widthwise stretching ratio was changed to 3.7 times, the temperature during the second stage of widthwise stretching was changed to 220°C, the second stage of widthwise stretching ratio was changed to 1.2 times, and the temperature during relaxation treatment was changed to 220°C.

[0580] 4-4. PET Film 4

[0581] Referring to Japanese Patent Publication No. 2018-112635, a biaxially stretched PET film with a thickness of 25 μm according to Example 9 of the said publication was produced. The said PET film was designated as PET film 4.

[0582] 4-5. PET Film 5

[0583] As PET film 5, a commercially available biaxially stretched PET film (Toyobo Co., Ltd. product name "Cosmo Shine A4100", thickness 38 μm, with an easy-to-adhesive layer on one side) was prepared.

[0584] 4-6. PET Film 6

[0585] A biaxially stretched PET film 6 was obtained in the same manner as PET film 1, except that the first step of the stretching ratio in the width direction was changed to 3.5 times.

[0586] 4-7. PET Film 7

[0587] A biaxially stretched PET film 7 was obtained by making it the same as PET film 1, except that the first step of the stretching ratio in the width direction was changed to 3.4 times.

[0588] 4-8. PET Film 8

[0589] A biaxially stretched PET film 8 was obtained by making it the same as PET film 1, except that the lengthwise stretching ratio was changed to 3.1 times and the widthwise second-stage stretching ratio was changed to 1.2 times.

[0590] 4-9. PET Film 9

[0591] A biaxially stretched PET film 9 was obtained in the same manner as PET film 1, except that the lengthwise stretching ratio was changed to 4.0 times, the first step stretching ratio in the widthwise direction to 3.7 times, the temperature during the second step stretching in the widthwise direction to 220°C, the second step stretching ratio in the widthwise direction to 1.2 times, and the temperature during relaxation treatment to 220°C.

[0592] 5. Fabrication of Optical Laminates

[0593] 5-1. Optical laminate using PET film 1

[0594] [Example 1]

[0595] On a PET film 1 (see "4" above. ΔP: 0.150, nx-ny: 0.125, Re: 500 nm), the following coating solution 1 for an easy-adhesion layer was applied so that the wet mass was 5 g / m², and dried at 70°C for 30 seconds to form an easy-adhesion layer with a dry mass of 0.5 g / m².

[0596] Next, coating solution 2 for the uneven layer was applied onto the adhesive layer such that the wet mass was 12.5 g / m² (dry mass 5 g / m²), dried at 70°C for 30 seconds, and irradiated with 100 mJ / cm² of ultraviolet light to form an uneven layer with a dry thickness of 5 μm.

[0597] Next, a coating solution for an antifouling layer was applied onto the uneven surface layer such that the wet mass was 4 g / m² (dry mass 0.1 g / m²), dried at 60°C for 30 seconds, and irradiated with 200 mJ / cm² of ultraviolet light to form an antifouling layer with a dry thickness of 100 nm, thereby obtaining the optical laminate of Example 1.

[0598] <Coating Solution for Easy Adhesion Layer 1>

[0599] A coating solution prepared by mixing 33 parts by mass of polyester resin (Toyobo Corporation’s trade name “Byron UR-1400”) and 1 part by mass of a crosslinking agent (Mitsui Chemical Corporation’s trade name “Takenate D110N”), and diluting the mixture with a mixed solvent of methyl ethyl ketone and toluene in a mass ratio of 8:2 to a solid content of 10% by mass.

[0600] The manufacturing conditions of the optical laminate of Example 1, such as the wet mass of the uneven layer and the antifouling layer; the drying conditions of the uneven layer and the antifouling layer; the ultraviolet irradiation conditions of the uneven layer and the antifouling layer; and the drying thickness of the uneven layer and the antifouling layer, are defined as Manufacturing Method 1. An item of “Manufacturing Method” in Tables 1 to 4 that is “1” means that the manufacturing conditions described above are the same as those of the optical laminate of Example 1.

[0601] [Examples 2 to 5]

[0602] Optical laminates of Examples 2 to 5 were obtained in the same manner as Example 1, except that the coating solution 2 for the uneven layer was changed to the one listed in Table 1.

[0603] [Example 6]

[0604] On PET film 1 (see "4" above), the coating solution 1 for the adhesive layer was applied such that the wet mass was 5 g / m², and dried at 70°C for 30 seconds to form an adhesive layer with a dry mass of 0.5 g / m².

[0605] Next, coating solution 3 for the uneven layer was applied onto the adhesive layer such that the wet mass was 2.5 g / m² (dry mass 1 g / m²), dried at 70°C for 30 seconds, and irradiated with 100 mJ / cm² of ultraviolet light to form an uneven layer with a dry thickness of 1 μm.

[0606] Next, a coating solution for an antifouling layer was applied onto the uneven surface layer such that the wet mass was 4 g / m² (dry mass 0.1 g / m²), dried at 60°C for 30 seconds, and irradiated with 200 mJ / cm² of ultraviolet light to form an antifouling layer with a dry thickness of 100 nm, thereby obtaining the optical laminate of Example 6.

[0607] The manufacturing conditions of the optical laminate of Example 6, such as the wet mass of the uneven layer and the antifouling layer; the drying conditions of the uneven layer and the antifouling layer; the ultraviolet irradiation conditions of the uneven layer and the antifouling layer; and the drying thickness of the uneven layer and the antifouling layer, are referred to as Manufacturing Method 2.

[0608] [Comparative Examples 1 to 2, 4 to 7]

[0609] Optical laminates of Comparative Examples 1 to 2 and 4 to 7 were obtained in the same manner as Example 1, except that the coating solution 2 for the uneven layer was changed to the one listed in Table 1.

[0610] [Comparative Example 3]

[0611] On PET film 1 (see "4" above), the coating solution 1 for the adhesive layer was applied such that the wet mass was 5 g / m², and dried at 70°C for 30 seconds to form an adhesive layer with a dry mass of 0.5 g / m².

[0612] Next, coating solution 1 for the uneven layer was applied onto the adhesive layer such that the wet mass was 12.5 g / m² (dry mass 5 g / m²), dried at 50°C for 30 seconds, and irradiated with 100 mJ / cm² of ultraviolet light to form an uneven layer with a dry thickness of 5 μm.

[0613] Next, a coating solution for an antifouling layer was applied onto the uneven surface layer such that the wet mass was 4 g / m² (dry mass 0.1 g / m²), dried at 60°C for 30 seconds, and irradiated with 200 mJ / cm² of ultraviolet light to form an antifouling layer with a dry thickness of 100 nm, thereby obtaining the optical laminate of Comparative Example 3.

[0614] In addition, the manufacturing conditions of the optical laminate of Comparative Example 3, such as the wet mass of the uneven layer and the antifouling layer; the drying conditions of the uneven layer and the antifouling layer; the ultraviolet irradiation conditions of the uneven layer and the antifouling layer; and the drying thickness of the uneven layer and the antifouling layer, are designated as Manufacturing Method 3. An item of “Manufacturing Method” in Tables 1 to 4 that is “3” means that the manufacturing conditions described above are the same as those of the optical laminate of Comparative Example 3.

[0615] 5-2. Optical laminate using PET film 2

[0616] [Examples 7 to 12]

[0617] Optical laminates of Examples 7 to 12 were obtained in the same manner as Examples 1 to 6, except that PET film 1 was changed to PET film 2 of "4" above.

[0618] [Comparative Examples 8 to 14]

[0619] Optical laminates of Comparative Examples 8 to 14 were obtained in the same manner as Comparative Examples 1 to 7, except that PET film 1 was changed to PET film 2 of "4" above.

[0620] 5-3. Optical laminate using PET film 3

[0621] [Examples 13 to 18]

[0622] Optical laminates of Examples 13 to 18 were obtained in the same manner as Examples 1 to 6, except that PET film 1 was changed to PET film 3 of "4" above.

[0623] [Comparative Examples 15 to 21]

[0624] Optical laminates of Comparative Examples 15 to 21 were obtained in the same manner as Comparative Examples 1 to 7, except that PET film 1 was changed to PET film 3 of "4" above.

[0625] 5-4. Optical laminate with modified antifouling layer thickness

[0626] [Example 19]

[0627] The optical laminate of Example 19 was obtained in the same manner as Example 1, except that the thickness of the antifouling layer was changed to 90 nm.

[0628] [Example 20]

[0629] An optical laminate of Example 20 was obtained in the same manner as Example 1, except that the thickness of the antifouling layer was changed to 110 nm.

[0630]

[0631]

[0632]

[0633]

[0634] From Tables 1 to 4, it can be confirmed that the optical laminate of the example has excellent adhesion to the polyester film with a high plane orientation degree ΔP and the easy-to-adhere layer, and furthermore, excellent adhesion to the entire optical laminate, and can also suppress local defects.

[0635] 6. Verification of pencil hardness and rainbow staining

[0636] 6-1. Fabrication of Optical Laminates

[0637] [Examples 21 to 24]

[0638] Optical laminates of Examples 21 to 24 were obtained in the same manner as Example 1, except that PET film 1 was changed to PET films 6 to 9 of "4".

[0639] [Comparative Example 8]

[0640] An optical laminate of Comparative Example 8 was obtained in the same manner as Example 1, except that PET film 1 was changed to PET film 4 of "4" above.

[0641] [Comparative Example 9]

[0642] An optical laminate of Comparative Example 9 was obtained in the same manner as in Example 1, except that PET film 1 was changed to PET film 5 of "4" above. In addition, the optical laminate of Comparative Example 9 had an adhesive-easy layer, an uneven surface layer, and an antifouling layer formed on the side of PET film 5 that did not have an adhesive-easy layer.

[0643] 6-2. Evaluation

[0644] For the optical laminates obtained in Examples 1, 7, 13, 21 to 24 and Comparative Examples 8 to 9, measurements and evaluations of (1) and (2) below were performed. The results are shown in Table 5.

[0645] (1) Pencil hardness

[0646] The optical laminates obtained in Examples 1, 7, 13, 21 to 24 and Comparative Examples 8 to 9 were heated at 100°C for 10 minutes. Pencil hardness was measured for the heated optical laminates in accordance with the scratch hardness (pencil method) of JIS K 5600-5-4: 1999. Specifically, pencil hardness was measured by moving a pencil having a predetermined hardness on the antifouling layer side of the optical laminate at a speed of 1.4 mm / sec with a load of 500 g at an angle of 45° to the surface of the sample. After applying a load to the optical laminate sample, the sample was heated again at 100°C for 10 minutes before visually evaluating the scratch.

[0647] For each sample, the above operation was performed three times using a pencil of each hardness. At this time, among the pencils that did not have a single scratch, the hardest one was designated as the pencil hardness of that sample.

[0648] (2) Rainbow stain

[0649] On the viewing-side polarizing plate of the image display device (1) configured as described below, the PET film side of the optical laminate of the example and comparative example was placed so that it faced the polarizing plate side. Subsequently, the image display device was turned on in a dark room environment, observed from various angles with the naked eye, and the presence or absence of rainbow stains was evaluated according to the following criteria. The evaluators consisted of a total of 20 healthy people, with 5 people from each age group from their 20s to 50s, who had a corrected visual acuity of 1.0 or higher.

[0650] The atmosphere during the evaluation was set to a temperature of 23±5℃ and a relative humidity of 40% or more and 65% or less. In addition, prior to the start of the evaluation, the target sample was exposed to the above atmosphere for at least 30 minutes, and then the evaluation was performed.

[0651] A: More than 16 people answered that they could not acknowledge the rainbow stain.

[0652] B: 11 to 15 people answered that they could not acknowledge the rainbow stain.

[0653] C: Fewer than 10 people answered that they could not acknowledge the rainbow stain.

[0654] <Configuration of the image display device (1)>

[0655] (1) Display element: A tricolor-independent organic EL display element with a microcavity structure (coverage rate of BT. 2020-2 based on CIE-xy chromaticity: 77%).

[0656] (2) Light source side polarizer: None

[0657] (3) Viewer-side polarizer: A polarizer in which a TAC film is used as a polarizer protection film for a polarizer made of PVA and iodine. It is positioned so that the direction of the polarizer's absorption axis is parallel to the horizontal direction of the screen.

[0658] (4) Size: 10 inches diagonally

[0659]

[0660] From Table 4, it can be seen that the optical laminate of the example using a polyester film satisfying Equations 1-1 and 1-2 can suppress rainbow stains caused by in-plane phase difference and also improve the pencil hardness of the optical laminate. Explanation of the symbols

[0661] 10: Polyester film 20: Easy-adhesion layer 30: Uneven surface 40: Antifouling layer 100: Optical laminate

Claims

Claim 1 An optical laminate having an adhesive layer, an uneven layer, and an antifouling layer on a polyester film, wherein when the refractive index in the direction of the ground axis within the plane of the polyester film is defined as nx, the refractive index in the direction perpendicular to the ground axis within the same plane as ny, and the refractive index in the thickness direction of the polyester film as nz, the polyester film satisfies the following Equation 1-2, and when the uneven layer is defined as Ssk for the three-dimensional skewness of the surface of the uneven layer and Sa for the three-dimensional arithmetic mean roughness of the surface of the uneven layer, Ssk and Sa satisfy the following Equations 2-1 and 2-3. [In Equation 1-2, "ΔP" represents "((nx+ny) / 2)-nz".][In Equation 2-1, "A" represents "log 10 Represents "(Sa[㎛]×100 / Ssk)". However, 0 <Ssk이다.] Claim 2 An optical laminate according to claim 1, wherein the polyester film further satisfies the following formula 1-1. Claim 3 An optical laminate according to claim 1 or 2, wherein the Ssk of the uneven layer satisfies the following formula 2-2. Claim 4 An optical laminate according to claim 1 or 2, wherein the Ssk of the uneven surface layer is 0.10 or more and 0.40 or less. Claim 5 An optical laminate according to claim 1 or 2, wherein the thickness of the antifouling layer is 1 nm or more and 200 nm or less. Claim 6 An optical laminate according to claim 1 or 2, wherein the contact angle of the antifouling layer surface with respect to pure water is 80 degrees or more. Claim 7 An optical laminate according to claim 1 or 2, wherein the luminous reflectance Y value measured at an angle of light incidence of 5 degrees from the side having the antifouling layer is 3.0% or less. Claim 8 An optical laminate according to claim 1 or 2, wherein the thickness of the polyester film is 10㎛ or more and 75㎛ or less. Claim 9 A polarizing plate having a polarizer, a first transparent protective plate disposed on one side of the polarizer, and a second transparent protective plate disposed on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is an optical laminate as described in claim 1 or 2, and the optical laminate is disposed such that the surface of the antifouling layer faces the opposite side of the polarizer. Claim 10 A surface plate for an image display device having an optical laminate bonded to a resin plate or a glass plate, wherein the optical laminate is the optical laminate described in claim 1 or 2, and the optical laminate is arranged such that the surface of the antifouling layer faces the opposite side to the resin plate or the glass plate. Claim 11 An image display device having a surface on which the antifouling layer side of the optical laminate described in claim 1 or 2 is arranged to face opposite to the display element, and the optical laminate is arranged on the surface.

Citation Information

Patent Citations

  • Light source-side polarizer protection film, polarizing plate using the same, and liquid crystal display device

    JP2019124914A

  • Anti-glare film and polarizing plate using the same

    KR1020140075508A

  • Antiglare film and polarizing plate provided with the same

    JP2016504621A

  • Image display device

    KR1020110059522A